Polycarbonate resin composition and molded circuit parts for communication devices
By adding circuit formation stabilizers, fire retardants and fluoride drip inhibitors to the aromatic polycarbonate resin, the problem of insufficient comprehensive performance of electromagnetic compatibility, weather resistance and long-term durability in the prior art under high frequency bandwidth is solved, and the excellent performance of composite materials in these aspects is achieved.
Patent Information
- Application Number
- JP2021042357
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-03-16
AI Technical Summary
The prior art is difficult to simultaneously realize the comprehensive performance of broadband antenna materials with high frequency bandwidth in electromagnetic compatibility, weather resistance and long-term durability.
Using a composite material containing aromatic polycarbonate resin, circuit formation stabilizer, fire retardant and fluoride drip inhibitor, the electromagnetic compatibility, fire retardant and long-term durability of the material is improved by optimizing the proportion and combination of these components.
The excellent performance of the material under high frequency bandwidth is achieved, including low dielectric constant, good electromagnetic compatibility, strong fire resistance and long-term weather resistance.
Smart Images

Figure 0007666953000001 
Figure 0007666953000002 
Figure 0007666953000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition comprising an aromatic polycarbonate resin, a circuit formation stabilizer, a flame retardant and a fluorine-containing drip inhibitor. More specifically, the present invention relates to a polycarbonate resin composition which has strength, appearance, flame retardancy and low dielectric properties as well as good adhesion to a metal thin film during circuit formation and long-term durability. [Background technology]
[0002] Polycarbonate resin is excellent in transparency, impact resistance, heat resistance, and dimensional stability, and is therefore used as an engineering plastic in a wide range of fields, such as housings for electrical and electronic devices, interior and exterior parts for automobiles, building materials, furniture, musical instruments, and miscellaneous goods. In this context, various methods for manufacturing antennas inside electronic devices such as mobile phones including smartphones are being considered. In particular, there is a demand for broadband antennas that can be used in relatively high frequency bands such as the Sub6 band, microwaves, and millimeter wave bands, and for methods for three-dimensionally designing such antennas in electronic devices. As one of the techniques for forming such three-dimensional antennas, laser irradiation three-dimensional circuit molding technology has attracted attention. This technology is, for example, a technology that uses a resin material in which a metal complex is dispersed, reduces the complex with laser light to use it as a catalyst nucleus, and can directly form a circuit such as an antenna by selective plating without an adhesive layer. As examples of such laser irradiation three-dimensional circuit molding technology, for example, a resin composition consisting of a polycarbonate resin and a specific conductive oxide (Patent Document 1) and a resin composition capable of appropriately forming a metal thin film under a wide range of laser irradiation conditions have been proposed (Patent Document 2), but in both cases, the dielectric properties are increased by the metal complex blended into the resin composition, and the radio wave loss required for an antenna that can be used in a high frequency band is increased, and these are insufficient. In addition, a technology that enables laser irradiation three-dimensional circuit molding without using a metal complex in the resin composition has been proposed (Patent Document 3), but the polycarbonate resin used in the examples is insufficient in terms of long-term durability and low dielectric properties. In addition, a resin composition with excellent flame retardancy has been proposed in conjunction with the three-dimensionalization of electronic devices (Patent Document 4), but the good adhesion to the metal thin film and long-term durability required for a wide-band three-dimensional antenna are insufficient, and the dielectric properties are increased by the blended metal complex, making it insufficient. As described above, a polycarbonate resin composition that combines strength, appearance, flame retardancy, low dielectric properties, as well as good adhesion to the metal thin film during circuit formation and long-term durability has not been obtained. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-72338 A [Patent Document 2] WO2014 / 042070 publication [Patent Document 3] Special Publication No. 2016-516903 [Patent Document 4] WO2014 / 061460 publication Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a polycarbonate resin composition which combines strength, appearance, flame retardancy, low dielectric properties, as well as good adhesion to thin metal films during circuit formation and long-term durability. [Means for solving the problem]
[0005] As a result of intensive research to solve the above problems, the present inventors have found that by adding a circuit formation stabilizer, a flame retardant and a fluorine-containing drip-preventing agent to a specific aromatic polycarbonate resin, it is possible to obtain strength, appearance, flame retardancy and low dielectric properties that could not be obtained with conventional resin compositions, as well as low dielectric constant during circuit formation. The present inventors have found that it is possible to obtain a polycarbonate resin composition that has both good adhesion to a metal thin film and long-term durability, and have arrived at the present invention.
[0006] That is, according to the present invention, there is provided (1) a polycarbonate resin composition characterized by containing, relative to 100 parts by weight of (A) an aromatic polycarbonate resin excluding component B (component A), 10 to 5,000 parts by weight of (B) a circuit formation stabilizer (component B), 0.05 to 1,000 parts by weight of (C) a flame retardant (component C), and 0.1 to 50 parts by weight of (D) a fluorine-containing drip prevention agent (component D).
[0007] One of the more preferred embodiments of the present invention is (2) the polycarbonate resin composition according to configuration 1 above, characterized in that Component A is an aromatic polycarbonate resin containing 1 to 100 weight % of a polycarbonate-polydiorganosiloxane copolymer resin (Component A-1) consisting of a polycarbonate block represented by the following formula (1) and a polydiorganosiloxane block represented by the following formula (3), and the polydiorganosiloxane content in 100 weight % of Component A-1 is 0.05 to 20.0 weight %.
[0008] [ka]
[0009] (In the above general formula (1), R 1 and R 2 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each of these groups, they may be the same or different, a and b each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula (2):
[0010] [ka]
[0011] (In the above general formula (2), R 11 ,R 12 ,R 13 ,R 14 ,R 15 ,R 16 ,R 17 and R 18each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, represents a group selected from the group consisting of an aryl group having 6 to 14 atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, c is an integer of 1 to 10, and d is an integer of 4 to 7.
[0012] [ka]
[0013] (In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, e and f are each an integer of 1 to 4, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 4 or more and 150 or less, and X is a divalent aliphatic group having 2 to 8 carbon atoms.
[0014] One of the more preferred embodiments of the present invention is the polycarbonate resin composition according to the above-mentioned configuration 1 or 2, characterized in that (3) component B is a circuit formation stabilizer containing at least one compound selected from the group consisting of (B-1) a compound (component B-1) containing 10 mol % or more of carbonate structural units represented by the following formula (4) and (B-2) a compound (component B-2) containing 10 mol % or more of carbonate structural units represented by the following formula (5), excluding component B-1.
[0015] [ka]
[0016] (In the above general formula (4), R 1 and R 2 are each independently an alkyl group having 1 to 6 carbon atoms or a halogen atom, and R 3 and R 4 are each independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a halogen atom; R 5 represents a halogen atom, an alkyl group having 1 to 20 carbon atoms, or a cycloalkyl group having 3 to 20 carbon atoms, and n represents an integer of 0 to 10.
[0017] [ka]
[0018] (In the above general formula (5), R 1 and R 2 each independently represents a group selected from an alkyl group having 1 to 6 carbon atoms, an optionally substituted cycloalkyl group having 6 to 15 carbon atoms, an optionally substituted aryl group having 6 to 15 carbon atoms, and an optionally substituted aralkyl group having 7 to 15 carbon atoms; R 3 and R 4each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an optionally substituted cycloalkyl group having 6 to 15 carbon atoms, an optionally substituted aryl group having 6 to 15 carbon atoms, an optionally substituted aralkyl group having 7 to 15 carbon atoms, an optionally substituted alkenyl group having 2 to 20 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an optionally substituted cycloalkoxy group having 6 to 20 carbon atoms, an optionally substituted aryloxy group having 6 to 15 carbon atoms, an optionally substituted aralkyloxy group having 7 to 15 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each, they may be the same or different, a and b are natural numbers of 1 to 3, and W is a single bond or at least one group selected from the group consisting of groups represented by the above general formula (2).
[0019] One of the more preferred embodiments of the present invention is the polycarbonate resin composition according to any one of the above-mentioned configurations 1 to 3, characterized in that (4) Component C contains at least one flame retardant selected from the group consisting of halogen-based flame retardants, condensed phosphate ester compounds, phosphazene compounds, organometallic salt-based flame retardants, and silicone-based flame retardants.
[0020] One of the more preferred embodiments of the present invention is the polycarbonate resin composition according to the above-mentioned structure 3 or 4, characterized in that (5) component B-2 is a circuit formation stabilizer containing at least one member selected from the group consisting of: (B-2-1) a compound (B-2-1) composed of a structural unit (A) represented by the following formula (6), a structural unit (B) represented by the following formula (7), and a structural unit (C) represented by the following formula (8), wherein the proportion of structural unit (A) in all structural units is 5 to 15 mol%, the proportion of structural unit (B) is 20 to 60 mol%, and the proportion of structural unit (C) is 25 to 75 mol%, and (B-2-2) a compound (B-2-2) composed of a repeating structural unit (B) represented by the following formula (7) and a repeating structural unit (C) represented by the following formula (8), wherein the proportion of structural unit (B) in all structural units is 20 to 100 mol%, and the proportion of structural unit (C) is 0 to 80 mol%.
[0021] [ka]
[0022] (In the above general formula (6), R 1 and R 2 are each independently a hydrogen atom, a hydrocarbon group having 1 to 9 carbon atoms which may contain an aromatic group, or a halogen atom.
[0023] [ka]
[0024] (In the above general formula (7), R 3 and R 4 are each independently an alkyl group having 1 to 6 carbon atoms. X is a single bond, a substituted or unsubstituted alkylene group, a substituted or unsubstituted alkylidene group, a sulfur atom, or an oxygen atom.
[0025] [ka]
[0026] (In the above general formula (8), W is a single bond, a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkylidene group having 1 to 10 carbon atoms.)
[0027] One of the more preferred embodiments of the present invention is (6) the polycarbonate resin composition according to the above constitution 5, characterized in that the structural unit (A) is a structural unit derived from 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, the structural unit (B) is a structural unit derived from 2,2-bis(4-hydroxy-3-methylphenyl)propane, and the structural unit (C) is a structural unit derived from 2,2-bis(4-hydroxyphenyl)propane.
[0028] One of the more preferred embodiments of the present invention is the polycarbonate resin composition according to any one of the above structures 3 to 6, characterized in that (7) Component B-1 is a compound containing 20 mol % or more of structural units derived from 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, or 1,1-bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane.
[0029] One of the more preferred embodiments of the present invention is the polycarbonate resin composition according to any one of the above configurations 1 to 7, characterized in that it contains (8) 1 to 2,500 parts by weight of an inorganic filler (E) (Component E) per 100 parts by weight of Component A.
[0030] One of the more preferred embodiments of the present invention is the polycarbonate resin composition according to the above constitution 8, characterized in that (9) component E is at least one inorganic filler selected from the group consisting of glass, carbon fiber, talc, mica and wollastonite.
[0031] One of the more preferred embodiments of the present invention is (10) the polycarbonate resin composition according to the above configuration 8 or 9, characterized in that component E is at least one kind of glass fiber selected from the group consisting of (E-1) non-circular cross section glass fiber (component E-1) having a number average fiber length of 30 to 5000 μm, a ratio of the long axis to the short axis of the cross section (long axis / short axis) of 2.0 to 10.0, and a fiber diameter of 3.0 to 35.0 μm when the cross section is converted into a perfect circle, and (E-2) circular cross section glass fiber (component E-2) having a number average fiber length of 30 to 5000 μm and an average fiber diameter of 7.0 to 13.0 μm.
[0032] One of the more preferred embodiments of the present invention is the polycarbonate resin composition according to any one of the above configurations 8 to 10, characterized in that (11) Component E is glass fiber containing, relative to the total amount of the glass fibers, 52.0 to 57.0% by weight of SiO2, 13.0 to 17.0% by weight of Al2O3, 15.0 to 21.5% by weight of B2O3, 2.0 to 6.0% by weight of MgO, 2.0 to 6.0% by weight of CaO, 1.0 to 4.0% by weight of TiO2, and less than 1.5% by weight of F2, and the total amount of Li2O, Na2O and K2O is less than 0.6% by weight.
[0033] One of the more preferred embodiments of the present invention is (12) any one of the above configurations 1 to 11 for forming a circuit. The polycarbonate resin composition according to the present invention is
[0034] One of the more preferred embodiments of the present invention is (13) a molded circuit product for communication devices, which is made of the polycarbonate resin composition for forming circuits as described in the above constitution 12.
[0035] The present invention will be specifically described below.
[0036] (Component A: aromatic polycarbonate resin) The aromatic polycarbonate resin used in the present invention is an aromatic polycarbonate resin excluding component B. The aromatic polycarbonate resin is generally obtained by reacting a dihydroxy compound with a carbonate precursor by an interfacial polycondensation method or a melt transesterification method, or by polymerizing a carbonate prepolymer by a solid-phase transesterification method, or by polymerizing a cyclic carbonate compound by a ring-opening polymerization method. The dihydroxy component used here may be any dihydroxy component that is generally used as a dihydroxy component of aromatic polycarbonates, and may be a bisphenol or an aliphatic diol. As the bisphenol, a bisphenol represented by the following formula (9) is preferably used.
[0037] [ka]
[0038] [In the above general formula (9), R 1 and R 2 each independently represents a hydrogen atom, and when there are a plurality of each, they may be the same or different, a and b each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula (2):
[0039] [ka]
[0040] (In the above general formula (2), R 11 ,R 12 ,R 13 ,R 14 ,R 15 ,R 16 ,R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of such groups, they are the same. may be the same or different, c is an integer from 1 to 10, and d is an integer from 4 to 7.)]
[0041] Specific examples of bisphenols include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, bis(4-hydroxyphenyl)diphenylmethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-sulfonyldiphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'- Dimethyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl) propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane, and the like.
[0042] Examples of aliphatic diols include 2,2-bis-(4-hydroxycyclohexyl)-propane, 1,14-tetradecanediol, octaethylene glycol, 1,16-hexadecanediol, 4,4'-bis(2-hydroxyethoxy)biphenyl, bis{(2-hydroxyethoxy)phenyl}methane, 1,1-bis{(2-hydroxyethoxy)phenyl}ethane, 1,1-bis{(2-hydroxyethoxy)phenyl}-1-phenylethane, 2,2-bis{(2-hydroxyethoxy)phenyl}propane, 2,2-bis{(2-hydroxyethoxy)phenyl}propane, 2,2-bis{4-(2-hydroxyethoxy)-3,3'-biphenyl}propane, 2,2-bis{(2-hydroxyethoxy)-3-isopropylphenyl}propane, 2,2-bis{3-t-butyl-4-(2-hydroxyethoxy)phenyl}propane, 2,2-bis{(2-hydroxyethoxy)phenyl}butane, 2,2-bis{(2-hydroxyethoxy)phenyl}-4-methylpentane, 2,2-bis{(2-hydroxyethoxy)phenyl}octane, 1,1-bis{(2-hydroxyethoxy)phenyl}decane, 2,2-bis{3-bromo-4-(2-hydroxyethoxy)phenyl}propane, 2,2-bis{3,5-dimethyl-4-(2-hydroxyethoxy)phenyl}propane, 2,2-bis{3-cyclohexyl-4-(2-hydroxyethoxy)phenyl}propane, 1,1-bis{3-cyclohexyl-4-(2-hydroxyethoxy)phenyl}cyclohexane, bis{(2-hydroxyethoxy)phenyl}diphenyl fluorene, 9,9-bis{(2-hydroxyethoxy)phenyl}fluorene, 9,9-bis{4-(2-hydroxyethoxy)-3-methylphenyl}fluorene, 1,1-bis{(2-hydroxyethoxy)phenyl}cyclohexane, 1,1-bis{(2-hydroxyethoxy)phenyl}cyclopentane, 4,4'-bis(2-hydroxyethoxy)diphenyl ether, 4,4'-bis(2-hydroxyethoxy)-3,3'-dimethyldiphenyl ether, 1,3-bis[2-{(2-hydroxyethoxy)phenyl}propyl]benzene, 1,Examples of the 4-bis[2-{(2-hydroxyethoxy)phenyl}propyl]benzene include 1,4-bis{(2-hydroxyethoxy)phenyl}cyclohexane, 1,3-bis{(2-hydroxyethoxy)phenyl}cyclohexane, 4,8-bis{(2-hydroxyethoxy)phenyl}tricyclo[5.2.1.02,6]decane, 1,3-bis{(2-hydroxyethoxy)phenyl}-5,7-dimethyladamantane, 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5,5)undecane, 1,4:3,6-dianhydro-D-sorbitol (isosorbide), 1,4:3,6-dianhydro-D-mannitol (isomannide), and 1,4:3,6-dianhydro-L-iditol (isoidide).
[0043] Among these, aromatic bisphenols are preferred, and among these, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane and 4,4'-sulfonyldiphenol are particularly preferred. Among these, 2,2-bis(4-hydroxyphenyl)propane, which has excellent strength and good durability, is the most suitable. These may be used alone or in combination of two or more kinds.
[0044] The polycarbonate resin used as component A of the present invention may be a branched polycarbonate resin by using a branching agent in combination with the above dihydroxy compound. Examples of the trifunctional or higher polyfunctional aromatic compounds used in such branched polycarbonate resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1,1-bis(4- Examples of the trisphenols include trisphenols such as 1,4-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.
[0045] These polycarbonate resins are produced by a reaction means known per se for producing ordinary aromatic polycarbonate resins, for example, a method of reacting an aromatic dihydroxy component with a carbonate precursor such as phosgene or a carbonic acid diester. The basic means for the production method will be briefly described below.
[0046] In the reaction using, for example, phosgene as the carbonate precursor, the reaction is usually carried out in the presence of an acid binder and a solvent. As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide or an amine compound such as pyridine is used. As the solvent, for example, a halogenated hydrocarbon such as methylene chloride or chlorobenzene is used. In addition, a catalyst such as a tertiary amine or a quaternary ammonium salt can be used to promote the reaction. In this case, the reaction temperature is usually 0 to 40°C, and the reaction time is several minutes to 5 hours. The transesterification reaction using a carbonic acid diester as the carbonate precursor is carried out by a method in which a predetermined ratio of aromatic dihydroxy components is stirred with the carbonic acid diester while heating in an inert gas atmosphere, and the generated alcohol or phenol is distilled off. The reaction temperature varies depending on the boiling point of the generated alcohol or phenol, but is usually in the range of 120 to 300°C. The reaction is completed by reducing the pressure from the beginning and distilling off the generated alcohol or phenol. In addition, a catalyst usually used in the transesterification reaction can be used to promote the reaction. Examples of the carbonic acid diester used in the transesterification reaction include diphenyl carbonate, dinaphthyl carbonate, bis(diphenyl) carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, etc. Among these, diphenyl carbonate is particularly preferred.
[0047] In the present invention, a terminal terminator is used in the polymerization reaction. The terminal terminator is used to adjust the molecular weight, and the obtained polycarbonate resin has excellent thermal stability compared to those not having the terminals blocked, since the terminals are blocked. As such terminal terminators, monofunctional phenols represented by the following general formulas (10) to (12) can be mentioned.
[0048] [ka]
[0049] [In the above general formula (10), A is a hydrogen atom, an alkyl group having 1 to 9 carbon atoms, an alkylphenyl group (the alkyl portion has 1 to 9 carbon atoms), a phenyl group, or a phenylalkyl group (the alkyl portion has 1 to 9 carbon atoms), and r is an integer of 1 to 5, preferably 1 to 3.]
[0050] [ka]
[0051] [ka]
[0052] [In the above general formulas (11) and (12), Y is -RO-, -R-CO-O- or -RO-CO-, where R represents a single bond or a divalent aliphatic hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 5 carbon atoms, and n represents an integer of 10 to 50.]
[0053] Specific examples of the monofunctional phenols represented by the above general formula (10) include phenol, isopropylphenol, p-tert-butylphenol, p-cresol, p-cumylphenol, 2-phenylphenol, 4-phenylphenol, and isooctylphenol. The monofunctional phenols represented by the above general formulas (11) and (12) are phenols having a long-chain alkyl group or an aliphatic ester group as a substituent, and when they are used to block the ends of a polycarbonate resin, they not only function as a terminal terminator or molecular weight regulator, but also improve the melt flowability of the resin, making molding easier, and have the effect of lowering the water absorption rate of the resin, and are preferably used. The substituted phenols represented by the above general formula (11) are preferably those in which n is 10 to 30, particularly 10 to 26, and specific examples thereof include decylphenol, dodecylphenol, tetradecylphenol, hexadecylphenol, octadecylphenol, eicosylphenol, docosylphenol, and triacontylphenol. In addition, as the substituted phenols of the above general formula (12), compounds in which Y is -R-CO-O- and R is a single bond are suitable, and those in which n is 10 to 30, particularly 10 to 26, are preferred, and specific examples thereof include decyl hydroxybenzoate, dodecyl hydroxybenzoate, tetradecyl hydroxybenzoate, hexadecyl hydroxybenzoate, eicosyl hydroxybenzoate, docosyl hydroxybenzoate, and triacontyl hydroxybenzoate. Among these monofunctional phenols, the monofunctional phenols represented by the above general formula (10) are preferred, more preferably alkyl- or phenylalkyl-substituted phenols, and particularly preferably p-tert-butylphenol, p-cumylphenol, or 2-phenylphenol. It is desirable that the terminal terminator of these monofunctional phenols is introduced into the terminals of at least 5 mol%, preferably at least 10 mol%, of the total terminals of the obtained polycarbonate resin, and the terminal terminator may be used alone or in combination of two or more.
[0054] The polycarbonate resin used as component A of the present invention may be a polyester carbonate copolymerized with an aromatic dicarboxylic acid such as terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid or a derivative thereof, as long as it does not impair the spirit of the present invention.
[0055] The viscosity average molecular weight of the polycarbonate resin used as the A component of the present invention is preferably in the range of 12,000 to 50,000, more preferably in the range of 12,000 to 30,000, even more preferably in the range of 12,000 to 25,000, and most preferably in the range of 15,000 to 25,000. If the molecular weight exceeds 50,000, the melt viscosity may become too high, resulting in poor moldability, and if the molecular weight is less than 12,000, problems may occur in mechanical strength. The viscosity average molecular weight of the aromatic polycarbonate resin other than the A-1 component is preferably in the range of 10,000 to 16,000, more preferably in the range of 10,500 to 16,000, and even more preferably in the range of 11,000 to 15,800. If the molecular weight exceeds 16,000, the surface appearance may deteriorate, and if the molecular weight is less than 10,000, the strength may decrease. In the present invention, the viscosity average molecular weight is calculated by first determining the specific viscosity calculated by the following formula using an Ostwald viscometer from a solution prepared by dissolving 0.7 g of polycarbonate resin in 100 ml of methylene chloride at 20° C., and then inserting the determined specific viscosity into the following formula to determine the viscosity average molecular weight M.
[0056] Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 M 0.83 c=0.7
[0057] The polycarbonate resin used as component A of the present invention has a total Cl (chlorine) content in the resin of preferably 0 to 200 ppm, more preferably 0 to 150 ppm. If the total Cl content in the polycarbonate resin exceeds 200 ppm, it is not preferable because the color and thermal stability may deteriorate.
[0058] The component A of the present invention is preferably an aromatic polycarbonate resin containing 1 to 100% by weight of a polycarbonate-polydiorganosiloxane copolymer resin (component A-1) consisting of a polycarbonate block represented by the following formula (1) and a polydiorganosiloxane block represented by the following formula (3). The content of component A-1 is more preferably 1 to 70% by weight, and further preferably 5 to 50% by weight. If the content of component A-1 is less than 1% by weight, sufficient strength may not be obtained.
[0059] [ka]
[0060] [In the above general formula (1), R 1 and R 2 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each, they may be the same or different, a and b each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula (2):
[0061] [ka]
[0062] (In the above general formula (2), R 11 ,R 12 ,R 13 ,R 14 ,R 15 ,R 16 ,R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, c is an integer of 1 to 10, and d is an integer of 4 to 7.)
[0063] [ka]
[0064] [In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, or a group having 1 to 1 carbon atoms. e and f are each an integer of 1 to 4, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 4 or more and 150 or less. X is a divalent aliphatic group having 2 to 8 carbon atoms.]
[0065] Examples of the dihydric phenol (I) from which the carbonate structural unit represented by the general formula (1) is derived include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3 ,3'-biphenyl)propane, 2,2-bis(4-hydroxy-3-isopropylphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 4,4'-Dihydroxydiphenyl ether, 4,4'-Dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-Sulfonyldiphenol, 4,4'-Dihydroxydiphenyl sulfoxide , 4,4'-dihydroxydiphenyl sulfide, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,Examples of such benzene derivatives include 4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, and 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane.
[0066] Among these, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among these, 2,2-bis(4-hydroxyphenyl)propane, which has excellent strength and good durability, is most suitable. These may be used alone or in combination of two or more kinds.
[0067] In the carbonate structural unit represented by the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently preferably a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, and are particularly preferably a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group. 9and R 10 are each independently preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and particularly preferably a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. As the dihydroxyaryl-terminated polydiorganosiloxane (II) from which the carbonate structural unit represented by the above general formula (3) is derived, for example, a compound represented by the following general formula (I) is suitably used.
[0068] [ka]
[0069] p+q is preferably 4-120, more preferably 30-120, further preferably 30-100, and most preferably 30-60.
[0070] Next, a method for producing the above-mentioned preferred polycarbonate-polydiorganosiloxane copolymer resin will be described below. In advance, in a mixed solution of a water-insoluble organic solvent and an aqueous alkali solution, a mixed solution of chloroformate compounds containing a chloroformate of dihydric phenol (I) and / or a carbonate oligomer of dihydric phenol (I) having a terminal chloroformate group is prepared by reacting dihydric phenol (I) with a chloroformate-forming compound such as phosgene or a chloroformate of dihydric phenol (I) in a mixed solution of the water-insoluble organic solvent and the aqueous alkali solution. Phosgene is preferred as the chloroformate-forming compound.
[0071] In producing a chloroformate compound from a dihydric phenol (I), the entire amount of the dihydric phenol (I) from which the carbonate structural unit represented by the above general formula (1) is derived may be converted into a chloroformate compound at once, or a part of it may be added as a post-added monomer to the subsequent interfacial polycondensation reaction as a reaction raw material. The post-added monomer is added to rapidly advance the subsequent polycondensation reaction, and it is not necessary to add it if it is not necessary. The method of this chloroformate compound production reaction is not particularly limited, but it is usually preferable to carry out the reaction in a solvent in the presence of an acid binder. Furthermore, if desired, a small amount of an antioxidant such as sodium sulfite and hydrosulfide may be added, and it is preferable to add it. The proportion of the chloroformate-forming compound used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. In addition, when phosgene, which is a suitable chloroformate-forming compound, is used, a method of blowing gasified phosgene into the reaction system can be preferably adopted.
[0072] Examples of the acid binder include alkalis such as sodium hydroxide and potassium hydroxide. Examples of the acid binder include alkali metal hydroxides, alkali metal carbonates such as sodium carbonate and potassium carbonate, and organic bases such as pyridine, or mixtures thereof. The proportion of the acid binder used may be determined appropriately in consideration of the stoichiometric ratio (equivalents) of the reaction, as described above. Specifically, it is preferable to use 2 equivalents or a slightly excess amount of the acid binder per mole of the dihydric phenol (I) used to form the chloroformate compound of the dihydric phenol (I) (usually 1 mole corresponds to 2 equivalents).
[0073] As the solvent, a solvent inert to various reactions, such as those used in the production of known polycarbonates, may be used alone or as a mixture of solvents.Typical examples include hydrocarbon solvents such as xylene, and halogenated hydrocarbon solvents such as methylene chloride and chlorobenzene.In particular, halogenated hydrocarbon solvents such as methylene chloride are preferably used.
[0074] The pressure in the reaction for producing the chloroformate compound is not particularly limited, and may be normal pressure, elevated pressure, or reduced pressure, but it is usually advantageous to carry out the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C, and since the reaction often generates heat, it is preferable to cool the reaction with water or ice. The reaction time depends on other conditions and cannot be generally specified, but is usually carried out for 0.2 to 10 hours. The pH range in the reaction for producing the chloroformate compound can be determined using known interfacial reaction conditions, and the pH is usually adjusted to 10 or more.
[0075] In producing the polycarbonate-polydiorganosiloxane copolymer resin of the present invention, after preparing a mixed solution of chloroformate compounds containing a chloroformate of dihydric phenol (I) and a carbonate oligomer of dihydric phenol (I) having terminal chloroformate groups in this manner, the mixed solution is stirred and dihydroxyaryl-terminated polydiorganosiloxane (II) which derives the carbonate structural unit represented by general formula (3) is added at a rate of 0.01 mol / min or less per mol of the dihydric phenol (I) charged in preparing the mixed solution, thereby causing interfacial polycondensation of the dihydroxyaryl-terminated polydiorganosiloxane (II) and the chloroformate compound, thereby obtaining a polycarbonate-polydiorganosiloxane copolymer resin.
[0076] The polycarbonate-polydiorganosiloxane copolymer resin can be made into a branched polycarbonate-polydiorganosiloxane copolymer resin by using a branching agent in combination with a dihydric phenol compound. Examples of the polyfunctional aromatic compounds having three or more functionalities used in such branched polycarbonate resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1,1-bis(4- Examples of the trisphenols include trisphenols such as 1,4-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.
[0077] The method for producing such a branched polycarbonate-polydiorganosiloxane copolymer resin is a method in which a branching agent is contained in the mixed solution during the reaction for producing the chloroformate compound. Alternatively, a method in which a branching agent is added during the interfacial polycondensation reaction after the completion of the formation reaction may be used. The proportion of carbonate constituent units derived from the branching agent is preferably 0.005 to 1.5 mol %, more preferably 0.01 to 1.2 mol %, and particularly preferably 0.05 to 1.0 mol %, based on the total amount of carbonate constituent units constituting the copolymer resin. The amount of branched structures is 1 It can be calculated by H-NMR measurement.
[0078] The pressure in the system during the polycondensation reaction can be reduced, normal, or increased, but is usually preferably normal pressure or the natural pressure of the reaction system. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during the polymerization, it is desirable to cool the reaction with water or ice. The reaction time varies depending on other conditions such as the reaction temperature and cannot be generally specified, but is usually carried out for 0.5 to 10 hours. In some cases, the obtained polycarbonate-polydiorganosiloxane copolymer resin is appropriately subjected to physical treatment (mixing, fractionation, etc.) and / or chemical treatment (polymer reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a desired reduced viscosity [η SP The resulting reaction product (crude product) can be subjected to various post-treatments such as known separation and purification methods to recover a polycarbonate-polydiorganosiloxane copolymer resin of a desired purity (degree of purification).
[0079] The content of the polydiorganosiloxane block represented by the following general formula (13) in the above general formula (3) is preferably 1.0 to 20.0 wt %, more preferably 1.0 to 15.0 wt %, even more preferably 1.0 to 10.0 wt %, and most preferably 1.0 to 8.0 wt %, based on the total weight of the polycarbonate resin composition.
[0080] [ka]
[0081] (In the above general formula (13), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 4 or more and 150 or less.
[0082] The polydiorganosiloxane content in 100% by weight of component A-1 is preferably 0.05 to 20.0% by weight, more preferably 0.5 to 15.0% by weight, and even more preferably 1.0 to 10.0% by weight. If the content is less than 0.05% by weight, the strength may be insufficient, and if it exceeds 20.0% by weight, the appearance may be deteriorated due to the polydiorganosiloxane.
[0083] (Component B: Circuit formation stabilizer) The circuit formation stabilizer used as component B in the present invention is a compound capable of improving the adhesion and long-term durability of a circuit formed by laser irradiation. The circuit formation stabilizer is preferably a compound containing at least one selected from the group consisting of (B-1) a compound (component B-1) containing 10 mol % or more of a carbonate structural unit represented by the following formula (4) and (B-2) a compound (component B-2) containing 10 mol % or more of a carbonate structural unit represented by the following formula (5) excluding component B-1. Only one type of circuit formation stabilizer may be used, or two or more types may be used in combination.
[0084] [ka]
[0085] (In the above general formula (4), R 1 and R 2 are each independently an alkyl group having 1 to 6 carbon atoms or a halogen atom, and R 3 and R 4 are each independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a halogen atom; R 5 represents a halogen atom, an alkyl group having 1 to 20 carbon atoms, or a cycloalkyl group having 3 to 20 carbon atoms, and n represents an integer of 0 to 10.
[0086] [ka]
[0087] (In the above general formula (5), R1 , R 2 each independently represents a group selected from an alkyl group having 1 to 6 carbon atoms, an optionally substituted cycloalkyl group having 6 to 15 carbon atoms, an optionally substituted aryl group having 6 to 15 carbon atoms, and an optionally substituted aralkyl group having 7 to 15 carbon atoms; R 3 , R 4 each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an optionally substituted cycloalkyl group having 6 to 15 carbon atoms, an optionally substituted aryl group having 6 to 15 carbon atoms, an optionally substituted aralkyl group having 7 to 15 carbon atoms, an optionally substituted alkenyl group having 2 to 20 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an optionally substituted cycloalkoxy group having 6 to 20 carbon atoms, an optionally substituted aryloxy group having 6 to 15 carbon atoms, an optionally substituted aralkyloxy group having 7 to 15 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each, they may be the same or different, a and b are natural numbers of 1 to 3, and W is a single bond or at least one group selected from the group consisting of groups represented by the above general formula (2).
[0088] In the B-1 component, the ratio of the carbonate structural unit represented by the above formula (4) to the total structural units of 100 mol% is preferably 10 mol% or more, more preferably 15 mol% or more, even more preferably 20 mol% or more, particularly preferably 30 mol% or more, and most preferably 50 mol% or more. If the ratio of the structural unit is less than 10 mol%, the radio wave loss reduction effect, adhesion of the metal thin film, and long-term durability may be poor. The upper limit of the content is preferably 100 mol%.
[0089] The dihydric phenol from which the carbonate structural unit (A) represented by the above formula (4) is derived is 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-isopropylphenyl)cyclohexane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(3,5-dibromo-4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxy-3-isopropylphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(3,5-dibromo-4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, and the like. Preferred dihydric phenols are building blocks derived from 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)cyclohexane or 1,1-bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane, and particularly preferred dihydric phenols are 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane and / or 1,1-bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane.
[0090] Furthermore, carbonate bond repeating units derived from other dihydric phenols may be contained as long as the objects and characteristics of the present invention are not impaired.Representative examples of such other dihydric phenols include 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, hydroquinone, resorcinol, 4,4'-dihydroxydiphenyl, bis(4-hydroxyphenyl)methane, bis{(4-hydroxy-3,5-dimethyl)phenyl}methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane (bis Phenol A), 2,2-bis{(4-hydroxy-3-methyl)phenyl}propane, 2,2-bis{(4-hydroxy-3-phenyl)phenyl}propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)-3-methylbutane, 2,2-bis(4-hydroxyphenyl)-3,3-dimethylbutane, 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 2,2-bis(4-hydroxyphenyl)pentane, 3,3-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl) 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, 1,1-(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1'-bis-(4-hydroxyphenyl)-o-diisopropylbenzene, 1,1'-bis-(4-hydroxyphenyl)-meta-diisopropylbenzene, 1,1'-bis-(4-hydroxyphenyl)-para-diisopropylbenzene, 1,3-bis(4-hydroxyphenyl)- Examples of the dihydric phenol include 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl ketone, 4,4'-dihydroxydiphenyl ether and 4,4'-dihydroxydiphenyl ester, 1,1-bis(4-hydroxyphenyl)-2-methylpropane, and 2,2-bis(4-hydroxyphenyl)-4-methylpentane, which can be used alone or in combination of two or more. The most preferred dihydric phenol is bisphenol C.
[0091] The B-2 component is a compound containing 10 mol % or more of carbonate structural units represented by the above formula (5) excluding the B-1 component. The content is preferably 15 to 100 mol %, more preferably 20 to 100 mol %, and further preferably 30 to 100 mol %. If the content is less than 10 mol %, the circuit formation stability and transmission characteristics may be poor.
[0092] The carbonate structural unit represented by the above general formula (5) is usually derived from a dihydroxy compound and a carbonate precursor.
[0093] Examples of dihydroxy compounds from which the carbonate structural unit represented by the above general formula (5) is derived include 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(3-ethyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-isopropylphenyl)propane, 2,2-bis(4-hydroxy-3-isobutylphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4- hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-phenylphenyl)propane, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(3-ethyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-isopropylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-isobutylphenyl)cyclohexane, 1, 1-bis(3-t-butyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(3,5-dimethyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-phenylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane, bis(4-hydroxy-3-methylphenyl)methane, 1,1-bis(4- 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, and the like.
[0094] Among them, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3-phenylphenyl)propane, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-phenylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are preferred, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are more preferred, and 2,2-bis(4-hydroxy-3-methylphenyl)propane is the most preferred.
[0095] The component B-2 is preferably a circuit formation stabilizer containing at least one selected from the group consisting of: (B-2-1) a compound (component B-2-1) composed of a structural unit (A) represented by the following formula (6), a structural unit (B) represented by the following formula (7), and a structural unit (C) represented by the following formula (8), in which the proportion of structural unit (A) in all structural units is 5 to 15 mol%, the proportion of structural unit (B) is 20 to 60 mol%, and the proportion of structural unit (C) is 25 to 75 mol%, and (B-2-2) a compound (component B-2-2) composed of a repeating structural unit (B) represented by the following formula (7) and a repeating structural unit (C) represented by the following formula (8), in which the proportion of structural unit (B) in all structural units is 20 to 100 mol%, and the proportion of structural unit (C) is 0 to 80 mol%.
[0096] [ka]
[0097] (In the above general formula (6), R 1 and R 2 are each independently a hydrogen atom, a hydrocarbon group having 1 to 9 carbon atoms which may contain an aromatic group, or a halogen atom.
[0098] [ka]
[0099] (In the above general formula (7), R 3 and R 4 are each independently an alkyl group having 1 to 6 carbon atoms or a halogen atom. X is a single bond, a substituted or unsubstituted alkylene group, a substituted or unsubstituted alkylidene group, a sulfur atom, or an oxygen atom.
[0100] [ka]
[0101] (In the above general formula (8), W is a single bond, a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkylidene group having 1 to 10 carbon atoms.)
[0102] In the structural unit (A) represented by the formula (6), R 1 and R 2 are preferably each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0103] The dihydric phenol from which the structural unit (A) is derived includes 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, etc. The most preferred dihydric phenol is 9,9-bis(4-hydroxy-3-methylphenyl)fluorene.
[0104] In the B-2-1 component, the ratio of the structural unit (A) to all structural units is 5 to 15 mol%, preferably 5 to 12 mol%, and more preferably 8 to 10 mol%. If the ratio of the structural unit (A) exceeds 15 mol%, the heat resistance is improved, but the strength and long-term durability of the circuit may be deteriorated. If the ratio of the structural unit (A) is less than 5 mol%, the strength may be deteriorated.
[0105] In the structural unit (B) represented by the formula (7), R 3and R 4 are preferably each independently an alkyl group having 1 to 6 carbon atoms, and X is preferably a single bond, a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkylidene group having 1 to 10 carbon atoms.
[0106] Examples of dihydric phenols from which the structural unit (B) is derived include 2,2-bis(4-hydroxy-3-methylphenyl)propane (hereinafter referred to as bisphenol C), 2,2-bis(4-hydroxy-3-isopropylphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, etc. The most preferred dihydric phenol is bisphenol C.
[0107] In the B-2-1 component, the ratio of the structural unit (B) to all structural units is 20 to 60 mol%, preferably 30 to 50 mol%. If the ratio of the structural unit (B) exceeds 60 mol%, the strength may be poor. If the ratio of the structural unit (B) is less than 20 mol%, the circuit formation stability may be poor.
[0108] Examples of dihydric phenols from which the structural unit (C) is derived include 2,2-bis(4-hydroxyphenyl)propane (hereinafter referred to as bisphenol A), 4,4'-dihydroxy-1,1-biphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl thioether, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 1,1-bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 4,4-bis(4-hydroxyphenyl)heptane, 2,2-bis(4-hydroxyphenyl)octane, and 1,1-bis(4-hydroxyphenyl)decane. The most preferred dihydric phenol is bisphenol A.
[0109] In the B-2-1 component, the ratio of the structural unit (C) to all structural units is 25 to 75 mol%, preferably 30 to 70 mol%, more preferably 35 to 65 mol%, and even more preferably 40 to 60 mol%. If the ratio of the structural unit (C) exceeds 75 mol%, the circuit formation stability may be poor. If the ratio of the structural unit (C) is less than 25 mol%, the strength may be poor.
[0110] Component B-1 may contain carbonate bond repeating units derived from dihydric phenols other than the structural units (A), (B) and (C) as long as the objects and characteristics of the present invention are not impaired.
[0111] Suitable examples of dihydric phenols from which structural units other than the structural units (A), (B) and (C) are derived include 2,6-dihydroxynaphthalene, hydroquinone, resorcinol, resorcinol substituted with an alkyl group having 1 to 3 carbon atoms, 3-(4-hydroxyphenyl)-1,1,3-trimethylindan-5-ol, 1-(4-hydroxyphenyl)-1,3,3-trimethylindan-5-ol, 6,6'-dihydroxy-3,3,3',3'-tetramethylspiroindane, 1-methyl-1,3-bis(4-hydroxyphenyl)-3-isopropylcyclohexane, 1-methyl-2-(4-hydroxyphenyl)-3-[1-(4-hydroxyphenyl)isopropyl]cyclohexane, 1,6-bis(4-hydroxyphenyl)-1,6-hexanedione and the like. Further details of such polycarbonates are described, for example, in WO03 / 080728, JP-A-6-172508, JP-A-8-27370, JP-A-2001-55435, and JP-A-2002-117580.
[0112] In the B-2-2 component, the structural units (B) and (C) are the same as those in the B-2-1 component. In the B-2-2 component, the proportion of the structural unit (B) relative to all structural units is 20 to 100 mol%, preferably 25 to 100 mol%, and more preferably 40 to 100 mol%. If the proportion of the structural unit (B) is less than 20 mol%, the dielectric properties will be high, and the adhesion and long-term durability of the metal thin film may decrease.
[0113] The circuit formation stabilizer used in the present invention is obtained by reacting a dihydric phenol with a carbonate precursor. Examples of the reaction method include an interfacial polycondensation method, a melt transesterification method, a solid-phase transesterification method of a carbonate prepolymer, and a ring-opening polymerization method of a cyclic carbonate compound. In the case of interfacial polycondensation, a terminal terminator of a monohydric phenol is usually used. In addition, it may be a branched polycarbonate obtained by polymerizing a trifunctional component, or a circuit formation stabilizer obtained by copolymerizing an aliphatic dicarboxylic acid, an aromatic dicarboxylic acid, and a vinyl monomer.
[0114] In a reaction using, for example, phosgene as a carbonate precursor, the reaction is usually carried out in the presence of an acid binder and a solvent. As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, or an amine compound such as pyridine, is used. As the solvent, for example, a halogenated hydrocarbon such as methylene chloride or chlorobenzene is used. In addition, a catalyst such as a tertiary amine or a quaternary ammonium salt can be used to promote the reaction. In this case, the reaction temperature is usually 0 to 40°C, and the reaction time is several minutes to 5 hours.
[0115] The transesterification reaction using, for example, a carbonic acid diester as a carbonate precursor is carried out by a method in which a predetermined ratio of aromatic dihydroxy components is heated and stirred with a carbonic acid diester under an inert gas atmosphere, and the alcohol or phenols produced are distilled off. The reaction temperature varies depending on the boiling point of the alcohol or phenols produced, but is usually in the range of 120 to 300°C. The reaction is completed by reducing the pressure from the beginning of the reaction and distilling off the alcohol or phenols produced. In order to promote the reaction, a catalyst usually used in transesterification reactions can also be used. Examples of the carbonic acid diester used in the transesterification reaction include diphenyl carbonate, dinaphthyl carbonate, bis(diphenyl)carbonate, dimethyl carbonate, diethyl carbonate, and dibutyl carbonate. Among these, diphenyl carbonate is particularly preferred.
[0116] Monofunctional phenols that are commonly used as end terminators can be used. In particular, in the case of a reaction using phosgene as a carbonate precursor, monofunctional phenols are generally used as end terminators to adjust molecular weight, and the obtained circuit formation stabilizer has excellent thermal stability compared to those that are not, since the ends are blocked by groups based on monofunctional phenols. Specific examples of the monofunctional phenols include phenol, m-methylphenol, p-methylphenol, m-propylphenol, p-propylphenol, 1-phenylphenol, 2-phenylphenol, p-tert-butylphenol, p-cumylphenol, isooctylphenol, and p-long chain alkylphenol.
[0117] The circuit formation stabilizer used in the present invention can be copolymerized with an aliphatic diol if necessary, such as isosorbide:1,4:3,6-dianhydro-D-sorbitol, tricyclodecane dimethanol (TCDDM), 4,8-bis(hydroxymethyl)tricyclodecane, tetramethylcyclobutanediol (TMCBD), 2,2,4,4-tetramethylcyclobutane-1,3-diol, mixed isomers, cis / trans-1,4-cyclohexanedimethanol (CHDM), cis / trans-1,4-bis(hydroxymethyl)cyclohexane, cyclohex-1,4-ylenedimethanol, tricyclohexyl ether, ... Examples of suitable cyclohexanedimethanol include trans-1,4-cyclohexanedimethanol (tCHDM), trans-1,4-bis(hydroxymethyl)cyclohexane, cis-1,4-cyclohexanedimethanol (cCHDM), cis-1,4-bis(hydroxymethyl)cyclohexane, cis-1,2-cyclohexanedimethanol, 1,1'-bi(cyclohexyl)-4,4'-diol, spiroglycol, dicyclohexyl-4,4'-diol, 4,4'-dihydroxybicyclohexyl, and poly(ethylene glycol).
[0118] The circuit formation stabilizer used in the present invention can be copolymerized with a fatty acid, if necessary, such as 1,10-dodecanedioic acid (DDDA), adipic acid, hexanedioic acid, isophthalic acid, 1,3-benzenedicarboxylic acid, terephthalic acid, 1,4-benzenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 3-hydroxybenzoic acid (mHBA), and 4-hydroxybenzoic acid (pHBA).
[0119] The circuit formation stabilizer used in the present invention includes a compound obtained by copolymerizing aromatic or aliphatic (including alicyclic) bifunctional carboxylic acids. The aliphatic bifunctional carboxylic acids are preferably α,ω-dicarboxylic acids. Examples of the aliphatic bifunctional carboxylic acids include linear saturated aliphatic dicarboxylic acids such as sebacic acid (decanedioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, and icosane diacid, and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid. These carboxylic acids may be copolymerized to the extent that the purpose is not hindered.
[0120] The circuit formation stabilizer used in the present invention can also be a branched circuit formation stabilizer by copolymerizing a constituent unit containing a trifunctional or higher polyfunctional aromatic compound as necessary. As the trifunctional or higher polyfunctional aromatic compound used in the branched circuit formation stabilizer, suitable examples include trisphenols such as 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2, 2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, and 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol. Among them, 1,1,1-tris(4-hydroxyphenyl)ethane is preferred. The constituent units derived from such polyfunctional aromatic compounds preferably account for 0.03 to 1.5 mol %, more preferably 0.1 to 1.2 mol %, and particularly preferably 0.2 to 1.0 mol %, of a total of 100 mol %, including the constituent units from other divalent components.
[0121] The branched structural unit may be derived not only from a polyfunctional aromatic compound, but also from a side reaction occurring during a polymerization reaction by a melt transesterification method without using a polyfunctional aromatic compound. 1It can be calculated by H-NMR measurement.
[0122] The content of component B is 10 to 5000 parts by weight, preferably 30 to 4600 parts by weight, and more preferably 100 to 4000 parts by weight, relative to 100 parts by weight of component A. If the content is less than 10 parts by weight, the dielectric properties will be high, and the adhesion and long-term durability of the metal thin film will be insufficient, while if it exceeds 5000 parts by weight, the strength will be insufficient.
[0123] (Component C: flame retardant) The polycarbonate resin composition of the present invention contains various compounds known as flame retardants. The incorporation of compounds used as flame retardants not only improves flame retardancy, but also improves, for example, antistatic properties, fluidity, rigidity, and thermal stability based on the properties of each compound. The content of component C is 0.05 to 1000 parts by weight, preferably 0.1 to 950 parts by weight, and more preferably 0.15 to 900 parts by weight, relative to 100 parts by weight of component A. If the content is less than 0.05 parts by weight, the flame retardancy is not improved, and if it exceeds 1000 parts by weight, the strength decreases and sufficient long-term durability is not obtained.
[0124] Examples of such flame retardants include: (1) organic metal salt flame retardants (e.g., organic alkali sulfonates ( (1) organic phosphorus-based flame retardants (e.g., monophosphate compounds, phosphate oligomer compounds, phosphonate oligomer compounds, phosphonitrile oligomer compounds, and phosphonic acid amide compounds); (2) silicone-based flame retardants made of silicone compounds; and (3) halogen-based flame retardants (e.g., brominated epoxy resins, brominated polystyrene, brominated polycarbonates (including oligomers), brominated polyacrylates, and chlorinated polyethylenes).
[0125] (1) Organic metal salt flame retardants The organometallic salt flame retardant is advantageous in that it can maintain heat resistance and can impart antistatic properties to a certain extent. The organometallic salt flame retardant most advantageously used in the present invention is a fluorine-containing organometallic salt compound. The fluorine-containing organometallic salt compound of the present invention refers to a metal salt compound consisting of an anion component consisting of an organic acid having a fluorine-substituted hydrocarbon group and a cation component consisting of a metal ion. More preferred examples include metal salts of fluorine-substituted organic sulfonic acids, metal salts of fluorine-substituted organic sulfates, and metal salts of fluorine-substituted organic phosphates. The fluorine-containing organometallic salt compounds can be used alone or in combination of two or more. Among them, metal salts of fluorine-substituted organic sulfonic acids are preferred, and metal salts of sulfonic acids having a perfluoroalkyl group are particularly preferred. Here, the number of carbon atoms in the perfluoroalkyl group is preferably in the range of 1 to 18, more preferably in the range of 1 to 10, and even more preferably in the range of 1 to 8.
[0126] The metals constituting the metal ions of the organic metal salt flame retardant are alkali metals or alkaline earth metals, and examples of the alkali metals include lithium, sodium, potassium, rubidium, and cesium, and examples of the alkaline earth metals include beryllium, magnesium, calcium, strontium, and barium. More preferably, they are alkali metals. Therefore, the preferred organic metal salt flame retardant is an alkali metal salt of perfluoroalkylsulfonic acid. Among these alkali metals, rubidium and cesium are preferred when a higher transparency is required, but they are not versatile and difficult to refine, which may result in a disadvantage in terms of cost. On the other hand, although they are advantageous in terms of cost and flame retardancy, lithium and sodium may conversely be disadvantageous in terms of transparency. Taking these into consideration, the alkali metals in the alkali metal salt of perfluoroalkylsulfonic acid can be used differently, but in all respects, potassium salt of perfluoroalkylsulfonic acid, which has an excellent balance of properties, is the most preferred. Such a potassium salt can also be used in combination with an alkali metal salt of perfluoroalkylsulfonic acid made of another alkali metal.
[0127] Examples of such perfluoroalkylsulfonic acid alkali metal salt include potassium trifluoromethanesulfonate, potassium perfluorobutanesulfonate, potassium perfluorohexanesulfonate, potassium perfluorooctane sulfonate, sodium pentafluoroethanesulfonate, sodium perfluorobutanesulfonate, sodium perfluorooctane sulfonate, lithium trifluoromethanesulfonate, lithium perfluorobutanesulfonate, lithium perfluoroheptanesulfonate, cesium trifluoromethanesulfonate, cesium perfluorobutanesulfonate, cesium perfluorooctane sulfonate, cesium perfluorohexanesulfonate, rubidium perfluorobutanesulfonate, and rubidium perfluorohexanesulfonate, and the like, and these can be used alone or in combination of two or more.Among these, potassium perfluorobutanesulfonate is particularly preferred.
[0128] The fluorine-containing organic metal salt preferably has a fluoride ion content of 50 ppm or less, more preferably 20 ppm or less, and even more preferably 10 ppm or less, as measured by ion chromatography. The lower the fluoride ion content, the better the flame retardancy and light resistance. The lower limit of the fluoride ion content can be substantially 0, but is preferably about 0.2 ppm in practical terms in consideration of the balance between the refining man-hours and the effect. The alkali metal salt of perfluoroalkylsulfonate having such a fluoride ion content is refined, for example, as follows. The alkali metal salt of perfluoroalkylsulfonate is dissolved in ion-exchanged water of 2 to 10 times the weight of the metal salt at a temperature in the range of 40 to 90°C (more preferably 60 to 85°C). The alkali metal salt of perfluoroalkylsulfonate is produced by a method of neutralizing perfluoroalkylsulfonic acid with an alkali metal carbonate or hydroxide, or a method of neutralizing perfluoroalkylsulfonyl fluoride with an alkali metal carbonate or hydroxide (more preferably the latter method). The ion-exchanged water is particularly preferably water having an electric resistance value of 18 MΩ·cm or more. The liquid in which the metal salt is dissolved is stirred at the above temperature for 0.1 to 3 hours, more preferably for 0.5 to 2.5 hours. Thereafter, the liquid is cooled to a temperature range of 0 to 40° C., more preferably 10 to 35° C. Cooling causes crystals to precipitate. The precipitated crystals are removed by filtration. In this way, a suitable purified alkali metal salt of perfluoroalkylsulfonic acid is produced.
[0129] The content of the fluorine-containing organometallic salt compound is preferably 0.05 to 6 parts by weight, more preferably 0.1 to 5 parts by weight, and further preferably 0.15 to 3 parts by weight, based on 100 parts by weight of component A. As the content is in such a preferred range, the expected effects (e.g., flame retardancy, antistatic property, etc.) of the blending of the fluorine-containing organometallic salt are exhibited more, and the adverse effect on the light resistance of the polycarbonate resin composition is reduced.
[0130] As the organic metal salt-based flame retardant other than the above-mentioned fluorine-containing organic metal salt compounds, metal salts of organic sulfonic acids not containing fluorine atoms are suitable. Examples of such metal salts include alkali metal salts of aliphatic sulfonic acids, alkaline earth metal salts of aliphatic sulfonic acids, alkali metal salts of aromatic sulfonic acids, and alkaline earth metal salts of aromatic sulfonic acids (none of which contain fluorine atoms).
[0131] Preferred examples of the aliphatic sulfonic acid metal salt include alkylsulfonic acid alkali (earth) metal salts, which can be used alone or in combination of two or more (herein, the term "alkali (earth) metal salt" is used to mean both alkali metal salts and alkaline earth metal salts). Preferred examples of the alkane sulfonic acid used in such alkylsulfonic acid alkali (earth) metal salts include methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, butanesulfonic acid, methylbutanesulfonic acid, hexanesulfonic acid, heptanesulfonic acid, octanesulfonic acid, etc., which can be used alone or in combination of two or more.
[0132] The aromatic sulfonic acid used in the alkali (earth) metal salt of aromatic sulfonate may be at least one acid selected from the group consisting of monomeric or polymeric aromatic sulfide sulfonic acids, aromatic carboxylic acids and ester sulfonic acids, monomeric or polymeric aromatic ether sulfonic acids, aromatic sulfonate sulfonic acids, monomeric or polymeric aromatic sulfonic acids, monomeric or polymeric aromatic sulfone sulfonic acids, aromatic ketone sulfonic acids, heterocyclic sulfonic acids, aromatic sulfoxide sulfonic acids, and condensates of aromatic sulfonic acids with methylene bonds, and these may be used alone or in combination of two or more kinds.
[0133] Specific examples of the aromatic sulfonic acid alkali (earth) metal salts include disodium diphenyl sulfide-4,4'-disulfonate, dipotassium diphenyl sulfide-4,4'-disulfonate, potassium 5-sulfoisophthalate, sodium 5-sulfoisophthalate, polysodium polyethylene terephthalate polysulfonate, calcium 1-methoxynaphthalene-4-sulfonate, disodium 4-dodecylphenyl ether disulfonate, polysodium poly(2,6-dimethylphenylene oxide) polysulfonate, polysodium poly(1,3-phenylene oxide) polysulfonate, polysodium poly(1,4-phenylene oxide) polysulfonate, polypotassium poly(2,6-diphenylphenylene oxide) polysulfonate, lithium poly(2-fluoro-6-butylphenylene oxide) polysulfonate, potassium sulfonate of benzenesulfonate, sodium benzenesulfonate, and sodium benzenesulfonate. Examples of suitable sulfonates include thoronium, magnesium benzenesulfonate, dipotassium p-benzenedisulfonate, dipotassium naphthalene-2,6-disulfonate, calcium biphenyl-3,3'-disulfonate, sodium diphenylsulfone-3-sulfonate, potassium diphenylsulfone-3-sulfonate, dipotassium diphenylsulfone-3,3'-disulfonate, dipotassium diphenylsulfone-3,4'-disulfonate, sodium α,α,α-trifluoroacetophenone-4-sulfonate, dipotassium benzophenone-3,3'-disulfonate, disodium thiophene-2,5-disulfonate, dipotassium thiophene-2,5-disulfonate, calcium thiophene-2,5-disulfonate, sodium benzothiophenesulfonate, potassium diphenylsulfoxide-4-sulfonate, a formalin condensate of sodium naphthalenesulfonate, and a formalin condensate of sodium anthracenesulfonate.
[0134] On the other hand, examples of the alkali (earth) metal salts of sulfates include, in particular, alkali (earth) metal salts of sulfates of monohydric and / or polyhydric alcohols, and examples of such sulfates of monohydric and / or polyhydric alcohols include methyl sulfate, ethyl sulfate, lauryl sulfate, hexadecyl sulfate, sulfates of polyoxyethylene alkylphenyl ethers, mono-, di-, tri-, and tetrasulfates of pentaerythritol, sulfates of lauric acid monoglyceride, sulfates of palmitic acid monoglyceride, and sulfates of stearic acid monoglyceride, etc. As the alkali (earth) metal salts of these sulfates, the alkali (earth) metal salt of lauryl sulfate is preferred.
[0135] Other examples of the alkali (earth) metal salts include alkali (earth) metal salts of aromatic sulfonamides, such as saccharin, N-(p-tolylsulfonyl)-p-toluenesulfonimide, N-(N'-benzylaminocarbonyl)sulfanilimide, and N-(phenylcarboxyl)sulfanilimide.
[0136] Among the above, preferred metal salts of fluorine-free organic sulfonic acids are alkali (earth) metal salts of aromatic sulfonates, and potassium salts are particularly preferred. When such alkali (earth) metal salts of aromatic sulfonates are used, the content is preferably 0.05 to 6 parts by weight, more preferably 0.10 to 5 parts by weight, and even more preferably 0.15 to 3 parts by weight, per 100 parts by weight of component A.
[0137] (2) Organophosphorus flame retardants As the organic phosphorus-based flame retardant of the present invention, a condensed phosphoric acid ester compound and a phosphazene compound are preferable.
[0138] 1) Condensed phosphate ester compounds As the condensed phosphate ester compound, an aryl phosphate compound is preferably used. Condensed phosphate ester compounds have a plasticizing effect, and are therefore advantageous in that they can improve molding processability. As the aryl phosphate compound, various phosphate compounds known as flame retardants can be used, but more preferably, one or more phosphate compounds represented by the following general formula (14) can be used.
[0139] [ka]
[0140] (In the above general formula (14), M represents a divalent organic group derived from a dihydric phenol, and Ar 1 , Ar 2 , Ar 3 , and Ar 4 Each of a, b, c, and d represents a monovalent organic group derived from a monohydric phenol. Each of a, b, c, and d is independently 0 or 1, and m is an integer of 0 to 5. In the case of a mixture of condensed phosphate esters having different degrees of polymerization m, m represents the average value thereof and is a value of 0 to 5.
[0141] The phosphate compound of the above formula may be a mixture of compounds having different m numbers, and in the case of such a mixture, the average m number is preferably in the range of 0.5 to 1.5, more preferably 0.8 to 1.2, even more preferably 0.95 to 1.15, and particularly preferably 1 to 1.14.
[0142] Specific preferred examples of the dihydric phenol from which M is derived include hydroquinone, resorcinol, bis(4-hydroxydiphenyl)methane, bisphenol A, dihydroxydiphenyl, dihydroxynaphthalene, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone, and bis(4-hydroxyphenyl)sulfide, and among these, resorcinol, bisphenol A, and dihydroxydiphenyl are preferred.
[0143] The above Ar 1 , Ar2 , Ar 3 , and Ar 4 Preferred specific examples of the monohydric phenol from which the formula (I) is derived include phenol, cresol, xylenol, isopropylphenol, butylphenol, and p-cumylphenol, and among these, phenol and 2,6-dimethylphenol are preferred.
[0144] In addition, such monohydric phenols may be substituted with halogen atoms, and specific examples of phosphate compounds having a group derived from such monohydric phenols include tris(2,4,6-tribromophenyl)phosphate, tris(2,4-dibromophenyl)phosphate, and tris(4-bromophenyl)phosphate.
[0145] On the other hand, specific examples of phosphate compounds not substituted with halogen atoms include monophosphate compounds such as tri(2,6-xylyl)phosphate, as well as phosphate oligomers mainly composed of resorcinol bis(di(2,6-xylyl)phosphate), phosphate oligomers mainly composed of 4,4-dihydroxydiphenyl bis(diphenyl phosphate), and phosphoric ester oligomers mainly composed of bisphenol A bis(diphenyl phosphate). (Here, "mainly composed" means that it may contain small amounts of other components with different degrees of polymerization, and more preferably means that the component of m=1 in the above formula (14) is contained in an amount of 80% by weight or more, more preferably 85% by weight or more, and even more preferably 90% by weight or more.)
[0146] 2) Phosphazene compounds Phosphazene compounds have a plasticizing effect, which is advantageous in terms of improving moldability. As the phosphazene compound, various phosphazene compounds conventionally known as flame retardants can be used, but phosphazene compounds represented by the following general formulas (15) and (16) are preferred.
[0147] [ka]
[0148] [ka]
[0149] (In the above general formulas (15) and (16), X 1 , X 2 , X 3 , X 4 represents an organic group that does not contain hydrogen, a hydroxyl group, an amino group, or a halogen atom, and r represents an integer of 3 to 10.
[0150] In the above formulas (15) and (16), X 1 , X 2 , X 3 , X 4 Examples of the halogen-free organic group represented by the formula (15) include an alkoxy group, a phenyl group, an amino group, an allyl group, etc. Among these, the cyclic phosphazene compound represented by the formula (15) is preferred, and further, X 1 , X 2 Cyclic phenoxyphosphazenes in which is a phenoxy group are particularly preferred.
[0151] The content of the organophosphorus flame retardant is preferably 1 to 1000 parts by weight, more preferably 10 to 800 parts by weight, and further preferably 20 to 700 parts by weight, based on 100 parts by weight of the A component.
[0152] (3) Silicone-based flame retardants The silicone compound used as the silicone flame retardant of the present invention improves flame retardancy by a chemical reaction during combustion. As the compound, various compounds proposed as flame retardants for aromatic polycarbonate resins can be used. It is considered that the silicone compound imparts flame retardant effect to the polycarbonate resin by forming a structure by itself or by combining with a component derived from the resin during combustion, or by a reduction reaction during the formation of the structure. Therefore, it is preferable that the silicone compound contains a group having high activity in such a reaction, and more specifically, it is preferable that the silicone compound contains a predetermined amount of at least one group selected from an alkoxy group and a hydrogen (i.e., Si-H group). The content ratio of such groups (alkoxy group, Si-H group) is preferably in the range of 0.1 to 1.2 mol / 100 g, more preferably in the range of 0.12 to 1 mol / 100 g, and even more preferably in the range of 0.15 to 0.6 mol / 100 g. The ratio is determined by measuring the amount of hydrogen or alcohol generated per unit weight of the silicone compound by an alkali decomposition method. The alkoxy group is preferably an alkoxy group having 1 to 4 carbon atoms, and a methoxy group is particularly preferred.
[0153] Generally, the structure of a silicone compound is composed of any combination of the following four types of siloxane units: M units: (CH3)3SiO 1 / 2 , H(CH3)2SiO 1 / 2 , H2(CH3)SiO 1 / 2 , (CH3)2(CH2=CH)SiO 1 / 2 , (CH3)2(C6H5)SiO 1 / 2 , (CH3)(C6H5)(CH2=CH)SiO 1 / 2 D units: (CH3)2SiO, H(CH3)SiO, H2SiO, H(C6H5)SiO, (CH3)(CH2=CH)SiO, (C6H5)2SiO and other difunctional siloxane units; T units: (CH3)SiO 3 / 2 , (C3H7)SiO 3 / 2 , HSiO 3 / 2 , (CH2=CH)SiO 3 / 2, (C6H5)SiO 3 / 2 and Q unit: a tetrafunctional siloxane unit represented by SiO2.
[0154] Specifically, the structure of the silicone compound used in the silicone-based flame retardant can be represented by the rational formula Dn, Tp, MmDn, MmTp, MmQq, MmDnTp, MmDnQq, MmTpQq, MmDnTpQq, DnTp, DnQq, and DnTpQq. Among these, preferred structures of the silicone compound are MmDn, MmTp, MmDnTp, and MmDnQq, and more preferred structures are MmDn and MmDnTp.
[0155] Here, the coefficients m, n, p, and q in the above rational formula are integers of 1 or more that represent the degree of polymerization of each siloxane unit, and the sum of the coefficients in each rational formula is the average degree of polymerization of the silicone compound. This average degree of polymerization is preferably in the range of 3 to 150, more preferably in the range of 3 to 80, even more preferably in the range of 3 to 60, and particularly preferably in the range of 4 to 40. The more preferable the range is, the more excellent the flame retardancy becomes. Furthermore, as described later, in the case of a silicone compound containing a predetermined amount of aromatic groups, the transparency and hue are also excellent.
[0156] Furthermore, when any of m, n, p, and q is a numerical value of 2 or more, the siloxane unit with that coefficient can be two or more types of siloxane units having different bonded hydrogen atoms or organic residues.
[0157] The silicone compound may be linear or branched. The organic residue bonded to the silicon atom is preferably an organic residue having 1 to 30 carbon atoms, more preferably 1 to 20 carbon atoms. Specific examples of such organic residues include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and decyl groups, cycloalkyl groups such as cyclohexyl groups, aryl groups such as phenyl groups, and aralkyl groups such as tolyl groups. More preferred are alkyl groups, alkenyl groups, or aryl groups having 1 to 8 carbon atoms. As the alkyl group, alkyl groups having 1 to 4 carbon atoms, such as methyl, ethyl, and propyl groups, are particularly preferred.
[0158] Furthermore, the silicone compound used as the silicone flame retardant preferably contains an aryl group, and more preferably the proportion of aromatic groups represented by the following general formula (17) (aromatic group amount) is 10 to 70% by weight (more preferably 15 to 60% by weight).
[0159] [ka]
[0160] (In the above general formula (17), each X is independently an OH group, a monovalent aryl group having 1 to 20 carbon atoms, represents an organic residue. n represents an integer of 0 to 5. Furthermore, when n is 2 or more in formula (17), each of the X's can be different from each other.
[0161] The silicone compound used as the silicone-based flame retardant may contain a reactive group other than the above-mentioned Si-H group and alkoxy group. Examples of such reactive groups include an amino group, a carboxy group, an epoxy group, a vinyl group, a mercapto group, and a methacryloxy group.
[0162] Suitable examples of silicone compounds having a Si-H group include silicone compounds containing at least one of the structural units represented by the following general formulas (18) and (19).
[0163] [ka]
[0164] [ka]
[0165] (In the above general formula (18) and formula (19), Z 1 ~Z 3 Each independently represents a hydrogen atom, a monovalent organic residue having 1 to 20 carbon atoms, or a compound represented by the following general formula (20). Each of α1 to α3 independently represents 0 or 1. m1 represents an integer of 0 or 1 or more. Furthermore, in formula (18), when m1 is 2 or more, the repeating unit can be a plurality of repeating units different from each other.
[0166] [ka]
[0167] (In the above general formula (20), Z 4 ~Z 8 Each independently represents a hydrogen atom or a monovalent organic residue having 1 to 20 carbon atoms. α4 to α8 each independently represent 0 or 1. m2 can be 0 or or an integer of 1 or more. Furthermore, when m2 in formula (20) is 2 or more, the repeating unit can be a plurality of repeating units different from each other.
[0168] Among the silicone compounds used in the silicone-based flame retardant, examples of the silicone compound having an alkoxy group include at least one compound selected from the compounds represented by general formula (21) and general formula (22).
[0169] [ka]
[0170] (In the above general formula (21), β1 represents a vinyl group, an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group and an aralkyl group having 6 to 12 carbon atoms. γ1, γ2, γ3, γ4, γ5, and γ6 represent an alkyl group and a cycloalkyl group having 1 to 6 carbon atoms, and an aryl group and an aralkyl group having 6 to 12 carbon atoms, at least one of the groups being an aryl group or an aralkyl group. δ1, δ2, and δ3 represent an alkoxy group having 1 to 4 carbon atoms.)
[0171] [ka]
[0172] (In the above general formula (22), β2 and β3 represent a vinyl group, an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group and an aralkyl group having 6 to 12 carbon atoms. γ7, γ8, γ9, γ10, γ11, γ12, γ13, and γ14 represent an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group and an aralkyl group having 6 to 12 carbon atoms, at least one group being an aryl group or an aralkyl. δ4, δ5, δ6, and δ7 represent an alkoxy group having 1 to 4 carbon atoms.)
[0173] The content of the silicone-based flame retardant is preferably 0.1 to 500 parts by weight, more preferably 0.5 to 400 parts by weight, and further preferably 1 to 300 parts by weight, per 100 parts by weight of component A. be.
[0174] (4) Halogen-based flame retardants Brominated polycarbonate (including oligomers) is particularly suitable as the halogen-based flame retardant of the present invention. Brominated polycarbonate has excellent heat resistance and can significantly improve flame retardancy. The brominated polycarbonate used in the present invention is a brominated polycarbonate compound in which the structural unit represented by the following general formula (23) accounts for at least 60 mol %, preferably at least 80 mol %, of all structural units, and is particularly preferably substantially composed of the structural unit represented by the following general formula (23).
[0175] [ka]
[0176] (In the above general formula (23), X is a bromine atom, and R is an alkylene group having 1 to 4 carbon atoms, an alkylidene group having 1 to 4 carbon atoms, or -SO2-.) In the formula (23), R preferably represents a methylene group, an ethylene group, an isopropylidene group, or -SO2-, and particularly preferably an isopropylidene group.
[0177] The brominated polycarbonate has a small amount of residual chloroformate group terminals, and the amount of terminal chlorine is preferably 0.3 ppm or less, more preferably 0.2 ppm or less. The amount of terminal chlorine can be determined by dissolving a sample in methylene chloride, adding 4-(p-nitrobenzyl)pyridine to react with terminal chlorine (terminal chloroformate), and measuring the amount with an ultraviolet-visible spectrophotometer (U-3200 manufactured by Hitachi, Ltd.). When the amount of terminal chlorine is 0.3 ppm or less, the thermal stability of the polycarbonate resin composition is improved, and molding at a higher temperature is possible, resulting in a polycarbonate resin composition with better molding processability.
[0178] In addition, the brominated polycarbonate preferably has few residual terminal hydroxyl groups. More specifically, the amount of terminal hydroxyl groups is preferably 0.0005 mol or less, more preferably 0.0003 mol or less, per mol of the constituent unit of the brominated polycarbonate. The amount of terminal hydroxyl groups is measured by dissolving a sample in deuterated chloroform and measuring the amount of terminal hydroxyl groups. 1 The amount of terminal hydroxyl groups can be determined by measurement using H-NMR. Such an amount of terminal hydroxyl groups is preferable because the thermal stability of the polycarbonate resin composition is further improved.
[0179] The specific viscosity of the brominated polycarbonate is preferably in the range of 0.015 to 0.1, more preferably 0.015 to 0.08, and is calculated according to the above-mentioned formula for calculating the specific viscosity used in calculating the viscosity average molecular weight of the polycarbonate resin, which is the component A of the present invention.
[0180] The content of the halogen-based flame retardant is preferably 0.5 to 1000 parts by weight, more preferably 1 to 800 parts by weight, and further preferably 20 to 700 parts by weight, relative to 100 parts by weight of the A component.
[0181] (Component D: Fluorine-containing drip prevention agent) The polycarbonate resin composition of the present invention contains a fluorine-containing drip-preventing agent. By using such a fluorine-containing drip-preventing agent in combination with the flame retardant, better flame retardancy can be obtained. Such a fluorine-containing drip-preventing agent can be a fluorine-containing polymer having fibril forming ability, and such a polymer can be polytetrafluoroethylene, a tetrafluoroethylene-based copolymer (e.g., tetrafluoroethylene / hexafluoropropylene copolymer, etc.), a partially fluorinated polymer as shown in U.S. Pat. No. 4,379,910, a polycarbonate resin produced from a fluorinated diphenol, etc., and preferably is polytetrafluoroethylene (hereinafter sometimes referred to as PTFE).
[0182] Polytetrafluoroethylene having fibril-forming ability (fibrillated PTFE) has an extremely high molecular weight, and shows a tendency to bond PTFE molecules together to become fibrous due to external action such as shear force. Its number average molecular weight is in the range of 1.5 million to tens of millions. The lower limit is more preferably 3 million. As disclosed in JP-A-6-145520, the number average molecular weight is calculated based on the melt viscosity of polytetrafluoroethylene at 380°C. That is, fibrillated PTFE has a melt viscosity at 380°C measured by the method described in said publication of 10 7 ~10 13 The range is preferably 108 ~10 12 The range is poise.
[0183] Such PTFE can be used in the form of a solid or an aqueous dispersion. In addition, such fibril-forming PTFE can improve dispersibility in resin, and can be used as a PTFE mixture mixed with other resins to obtain better flame retardancy and mechanical properties. As disclosed in JP-A-6-145520, a structure in which such fibrillated PTFE is the core and low molecular weight polytetrafluoroethylene is the shell is also preferably used.
[0184] Representative examples of commercially available fibrillated PTFE products include Teflon (registered trademark) 6J manufactured by DuPont-Mitsui Fluorochemicals Co., Ltd., and Polyflon MPA FA500 and F-201L manufactured by Daikin Chemical Industries, Ltd. Representative examples of commercially available aqueous dispersions of fibrillated PTFE include Fluon AD-1 and AD-936 manufactured by Asahi ICI Fluoropolymers Co., Ltd., Fluon D-1 and D-2 manufactured by Daikin Industries, Ltd., and Teflon (registered trademark) 30J manufactured by DuPont-Mitsui Fluorochemicals Co., Ltd.
[0185] The mixed form of fibrillated PTFE can be prepared by (1) mixing an aqueous dispersion of fibrillated PTFE with an aqueous dispersion or solution of an organic polymer and co-precipitating the mixture to obtain a co-aggregated mixture (methods described in JP-A-60-258263, JP-A-63-154744, etc.), (2) mixing an aqueous dispersion of fibrillated PTFE with dried organic polymer particles (method described in JP-A-4-272957), or (3) homogeneously mixing an aqueous dispersion of fibrillated PTFE with an organic polymer particle solution and extracting a co-aggregated mixture from the mixture. (4) a method of simultaneously removing the respective media (methods described in JP-A-06-220210, JP-A-08-188653, etc.), (5) a method of polymerizing a monomer that forms an organic polymer in an aqueous dispersion of fibrillated PTFE (method described in JP-A-09-95583), and (6) a method of uniformly mixing an aqueous dispersion of PTFE and an organic polymer dispersion, and then polymerizing a vinyl monomer in the mixed dispersion to obtain a mixture (method described in JP-A-11-29679, etc.). Examples of commercially available products of fibrillated PTFE in these mixed forms include "Metabrene A3800" (trade name) from Mitsubishi Rayon Co., Ltd., "BLENDEX B449" (trade name) from GE Specialty Chemicals, and "POLY TS AD001" (trade name) from Pacific Interchem Corporation.
[0186] The fibrillated PTFE is dispersed as finely as possible to prevent a decrease in mechanical strength. is preferable. As a means for achieving such fine dispersion, the fibrillated PTFE in the above mixed form is advantageous. Also, a method of directly supplying the aqueous dispersion form to a melt kneader is advantageous for fine dispersion. However, care must be taken that the aqueous dispersion form slightly deteriorates the hue. The ratio of fibrillated PTFE in the mixed form is preferably 10 to 80% by weight, more preferably 15 to 75% by weight, of the mixture (100% by weight). When the ratio of fibrillated PTFE is within this range, good dispersibility of the fibrillated PTFE can be achieved.
[0187] The content of component D is 0.1 to 50 parts by weight, preferably 0.3 to 45 parts by weight, and more preferably 0.5 to 40 parts by weight, relative to 100 parts by weight of component A. If the content of component D is less than 0.1 part by weight, flame retardancy cannot be obtained, and if it exceeds 50 parts by weight, a decrease in strength occurs.
[0188] (Component E: Inorganic filler) The resin composition of the present invention can contain an inorganic filler as component E. As the inorganic filler, any conventionally known inorganic filler can be used, but the inorganic filler that is preferably used is at least one inorganic filler selected from the group consisting of fibrous glass filler, plate-like glass filler, fibrous carbon filler, non-fibrous carbon filler, and silicate mineral, and among these, at least one inorganic filler selected from the group consisting of glass, carbon fiber, talc, mica, and wollastonite is preferred.
[0189] (E-1; Glass fiber) Examples of the glass fiber include glass fiber, metal-coated glass fiber, and milled glass fiber.
[0190] The glass fibers preferably used in the present invention include glass fibers (E glass fibers) having an E glass composition (a composition containing 52.0 to 56.0% by weight of SiO2, 12.0 to 16.0% by weight of Al2O3, 20.0 to 25.0% by weight in total of MgO and CaO, and 5.0 to 10.0% by weight of B2O3 relative to the total amount of glass fibers), NE glass composition (52.0 to 57.0% by weight of SiO2, 13.0 to 17.0% by weight of A, and 15.0 to 16.0% by weight of B2O3 relative to the total amount of glass fibers), and NE glass composition (52.0 to 57.0% by weight of SiO2, 13.0 to 17.0% by weight of A, and 15.0 to 16.0% by weight of B2O3 relative to the total amount of glass fibers). In addition to glass fibers having a composition containing 1.0 to 4.0% by weight of Li2O3, 15.0 to 21.5% by weight of B2O3, 2.0 to 6.0% by weight of MgO, 2.0 to 6.0% by weight of CaO, 1.0 to 4.0% by weight of TiO2, and less than 1.5% by weight of F2, and the total amount of Li2O, Na2O, and K2O is less than 0.6% by weight (NE glass fibers), glass fibers represented by S glass, D glass, etc. can be used, but NE glass fibers are particularly preferred due to their excellent dielectric properties.
[0191] In addition, if the content of SiO2 relative to the total amount of the NE glass fiber contained in the polycarbonate resin composition of the present invention is less than 52.0% by weight, the dielectric properties may be impaired and the water resistance and acid resistance may be reduced, which may cause deterioration of the glass fiber and the polycarbonate resin composition. On the other hand, if the content of SiO2 relative to the total amount of the glass fiber exceeds 57.0% by weight, the viscosity may become too high during spinning, making fiberization difficult. The content of SiO2 relative to the total amount of the glass fiber is preferably 52.5 to 56.8% by weight, more preferably 53.0 to 56.6% by weight, even more preferably 53.5 to 56.5% by weight, particularly preferably 53.8 to 56.3% by weight, and most preferably 54.0 to 56.2% by weight.
[0192] The content of Al2O3 relative to the total amount of glass fibers is preferably 13.3 to 16.5% by weight, more preferably 13.7 to 16.0% by weight, even more preferably 14.0 to 15.5% by weight, particularly preferably 14.3 to 15.3% by weight, and most preferably 14.5 to 15.1% by weight. If the content of Al2O3 relative to the total amount of glass fibers is less than 13.0% by weight, phase separation may occur easily and water resistance may deteriorate. On the other hand, if the content of Al2O3 relative to the total amount of glass fibers exceeds 17.0% by weight, the liquidus temperature increases, narrowing the working temperature range and making it difficult to manufacture the glass fibers.
[0193] The content of B2O3 relative to the total amount of glass fiber is preferably 15.5 to 21.0% by weight, more preferably 16.0 to 20.5% by weight, further preferably 16.5 to 20.0% by weight, and particularly preferably 17.5 to 19.4% by weight. If the content of B2O3 is less than 15.0% by weight, radio wave transmittance may be significantly impaired. On the other hand, if the content of B2O3 exceeds 21.5% by weight, the amount of volatilization of B2O3 during spinning is high, and glass fiber may be cut due to the dirt of B2O3 adhering to the vicinity of the bushing nozzle, which may cause problems in workability and productivity. Furthermore, homogeneous glass may not be obtained, and water resistance may become too poor.
[0194] The content of MgO relative to the total amount of glass fibers is preferably 2.5 to 5.9% by weight, more preferably 2.9 to 5.8% by weight, even more preferably 3.3 to 5.7% by weight, particularly preferably 3.6 to 5.3% by weight, and most preferably 4.0 to 4.8% by weight. If the content of MgO relative to the total amount of glass fibers is less than 2.0% by weight, striae may increase and the amount of volatilization of B2O3 may increase. On the other hand, if the content of MgO exceeds 6.0% by weight, phase separation may become strong, water resistance may decrease, and radio wave transmission may be significantly impaired.
[0195] The CaO content relative to the total amount of glass fibers is preferably 2.6 to 5.5% by weight, more preferably 3.2 to 5.0% by weight, further preferably 3.7 to 4.7% by weight, particularly preferably 3.9 to 4.5% by weight, and most preferably 4.0 to 4.4% by weight. If the CaO content relative to the total amount of glass fibers is less than 2.0% by weight, the melting property may become poor and the water resistance may become too poor. On the other hand, if the CaO content exceeds 6.0% by weight, the dielectric properties may be significantly impaired.
[0196] The content of TiO2 relative to the total amount of glass fibers is preferably 1.3 to 3.0% by weight, more preferably 1.5 to 2.5% by weight, even more preferably 1.6 to 2.3% by weight, particularly preferably 1.7 to 2.1% by weight, and most preferably 1.8 to 2.0% by weight. If the content of TiO2 relative to the total amount of glass fibers is less than 1.0% by weight, the effect of lowering the dielectric tangent, lowering the viscosity, suppressing melt separation during initial melting, and reducing the scum generated on the furnace surface may be reduced. On the other hand, if the content of TiO2 exceeds 4.0% by weight, phase separation may easily occur and chemical durability may be deteriorated.
[0197] The content of F2 relative to the total amount of glass fibers is preferably 0.1 to 1.4% by weight, more preferably 0.3 to 1.3% by weight, further preferably 0.4 to 1.2% by weight, particularly preferably 0.5 to 1.1% by weight, and most preferably 0.6 to 1.0% by weight. If the content of F2 relative to the total amount of glass fibers is 1.5% by weight or more, the glass may easily undergo phase separation and may have poor heat resistance. On the other hand, by including F2 in the glass fibers, not only the viscosity of the glass may be reduced to facilitate melting, but also the dielectric properties of the glass may be reduced.
[0198] The total content of Li2O, Na2O and K2O relative to the total amount of glass fibers is preferably 0.02 to 0.50% by weight, more preferably 0.03 to 0.40% by weight, further preferably 0.04 to 0.30% by weight, and particularly preferably 0.05 to 0.25% by weight. If the total content of Li2O, Na2O and K2O relative to the total amount of glass fibers is 0.6% by weight or more, the dielectric properties may become too high and the water resistance may also become poor. On the other hand, the inclusion of Li2O, Na2O and K2O may decrease the viscosity of glass, making it easier to melt the glass.
[0199] In addition, the NE glass fiber may contain impurities other than the above-mentioned components in a range of less than 0.4% by weight based on the total amount of the glass fiber. Impurities that the glass fiber may contain include Fe2O3, Cr2O3, ZrO2, MoO3, SO3, Cl2, etc. Among these, Since Fe2O3 affects the absorption of radiant heat in the molten glass and the coloring of the glass fibers, the content of Fe2O3 relative to the total amount of the glass fibers is preferably in the range of 0.05 to 0.15% by weight.
[0200] It is preferable that the composition has a ratio of the B2O3 content (wt%) to the TiO2 content (wt%) (B2O3 (wt%) / TiO2 (wt%)) in the range of 9.6 to 11.4. The ratio of the B2O3 content (wt%) to the TiO2 content (wt%) is more preferably in the range of 9.8 to 10.8, and even more preferably in the range of 10.0 to 10.4. By containing glass fibers in which the ratio of the B2O3 content (wt%) to the TiO2 content (wt%) satisfies the above range, it may be possible to achieve high radio wave transmittance while maintaining high productivity during glass melting and spinning.
[0201] In addition, in the NE glass fiber, the content of each of the above-mentioned components can be measured using an ICP optical emission spectrometer for the light element Li, and a wavelength dispersive X-ray fluorescence analyzer for the other elements.
[0202] As a measuring method, first, the polycarbonate resin composition is heated, for example, in a muffle furnace at 300 to 650 ° C for about 0.5 to 24 hours to decompose the organic matter. Next, the remaining glass fiber is placed in a platinum crucible and melted while stirring in an electric furnace at a temperature of 1550 ° C for 6 hours to obtain a homogeneous molten glass. Next, the obtained molten glass is poured onto a carbon plate to prepare glass cullet, which is then crushed and powdered. For Li, which is a light element, the glass powder is decomposed by alkali and acid melting, and then quantitatively analyzed using an ICP emission spectrometer. For other elements, the glass powder is molded into a disk shape using a press machine, and then quantitatively analyzed using a wavelength dispersive X-ray fluorescence analyzer. The results of these quantitative analyses are converted into oxides to calculate the content and total amount of each component, and the content of each component described above can be obtained from these values.
[0203] In the present invention, the glass fibers preferably have a number average fiber length of 30 to 5000 μm. If the number average fiber length of the glass fibers is less than 30 μm, the glass fiber reinforced resin molded product may not have sufficient tensile strength and impact strength. In addition, breakage of the glass fibers occurs during the production process of the polycarbonate resin composition, so it is difficult to make the number average fiber length of the glass fibers exceed 5000 μm. The number average fiber length is more preferably in the range of 100 to 3000 μm, even more preferably in the range of 150 to 2000 μm, particularly preferably in the range of 200 to 1000 μm, significantly more preferably in the range of 300 to 500 μm, and most preferably in the range of 315 to 450 μm.
[0204] The number average fiber length is measured by first decomposing the organic matter in the polycarbonate resin composition by, for example, heating it in a muffle at 300 to 650°C for about 0.5 to 24 hours. Next, the remaining glass fibers are transferred to a glass petri dish and dispersed on the surface of the petri dish using acetone. Next, the fiber lengths of 500 or more glass fibers dispersed on the surface are measured using a stereomicroscope, and the number average fiber length is calculated.
[0205] In the present invention, the glass fiber preferably has a noncircular cross section in which the ratio of the major axis to the minor axis of the cross-sectional shape (major axis / minor axis) is in the range of 2.0 to 10.0, and the fiber diameter when the cross-sectional area is converted into a perfect circle (hereinafter, sometimes referred to as converted fiber diameter) is in the range of 3.0 to 35.0 μm. When the glass fiber has such a cross section, the improvement rate of the tensile strength and the notched Charpy impact strength based on the tensile strength and the notched Charpy impact strength of the polycarbonate resin composition may be extremely high compared to when the glass fiber has a circular cross section.
[0206] In the glass fiber, the ratio of the major axis to the minor axis of the cross-sectional shape (major axis / minor axis) is more preferably in the range of 2.2 to 6.0, and even more preferably in the range of 3.2 to 4.5, from the viewpoint of achieving both high tensile strength and Charpy notched impact strength and ease of production of the glass fiber. When the glass fiber is formed by bundling a plurality of glass filaments, the cross-sectional shape of the glass fiber means the cross-sectional shape of the glass filaments forming the glass fiber.
[0207] In addition, in the glass fiber, from the viewpoint of achieving both high tensile strength and Charpy notched impact strength of the polycarbonate resin composition and ease of manufacture in producing a glass fiber or a glass fiber reinforced resin molded product, the equivalent fiber diameter is more preferably in the range of 6.0 to 20.0 μm, and more preferably 6.5 to 16.0 μm. When the glass fiber is formed by bundling a plurality of glass filaments, the fiber diameter of the glass fiber means the fiber diameter of the glass filaments forming the glass fiber.
[0208] In addition, in the glass fibers, the non-circular shape is preferably a cocoon shape, an ellipse shape, or an oval shape (meaning a rectangle with semicircular shapes on both ends, or a shape similar thereto), because this shape has excellent fluidity when producing a polycarbonate resin composition, and an oval shape is more preferable.
[0209] The polycarbonate resin composition of the present invention can contain both the glass fiber having a noncircular cross section and the glass fiber having a circular cross section. When the polycarbonate resin composition of the present invention contains both the glass fiber having a noncircular cross section and the glass fiber having a circular cross section, for example, the ratio of the content (wt%) of the circular cross section glass fiber to the content (wt%) of the noncircular cross section glass fiber (glass fiber having a circular cross section (wt%) / glass fiber having a noncircular cross section (wt%)) can be in the range of 0.1 to 1.0.
[0210] In the present invention, the glass fiber having a circular cross section preferably has a fiber diameter in the range of 7.0 to 13.0 μm. If the fiber diameter is less than 7.0 μm, the strength may be insufficient, and if it exceeds 13.0 μm, the processability of the glass fiber may be poor.
[0211] (E-2; Plate-shaped glass filler) Examples of the plate-like glass filler include glass flakes, metal-coated glass flakes, and metal oxide-coated glass flakes.
[0212] The glass flakes that are the base of the plate-shaped glass filler are plate-shaped glass fillers manufactured by a cylinder blowing method, a sol-gel method, or the like. The size of the raw material of the glass flakes can be selected from various sizes depending on the degree of crushing and classification. The average particle size of the glass flakes used as the raw material is preferably 10 to 1000 μm, more preferably 20 to 500 μm, and even more preferably 30 to 300 μm. The above range is because they are excellent in both handleability and moldability. Usually, the plate-shaped glass filler is cracked by melt-kneading with the resin, and the average particle size becomes small. The number average particle size of the plate-shaped glass filler in the thermoplastic resin composition is preferably 10 to 200 μm, more preferably 15 to 100 μm, and even more preferably 20 to 80 μm. The number average particle size is a value calculated by an image analyzer from an image obtained by observing the residue of the plate-shaped glass filler collected by high-temperature incineration of the molded product, dissolving with a solvent, and decomposing with a chemical, etc., by observing the image with an optical microscope. In addition, the calculation of this value is based on the method in which the flake thickness is used as a guide and flakes with a length less than this are not counted. The thickness is preferably 0.5 to 10 μm, more preferably 1 to 8 μm, and even more preferably 1.5 to 6 μm. A plate glass filler having the above number average particle size and thickness may achieve good mechanical strength, appearance, and moldability.
[0213] The glass composition of the plate-shaped glass filler is not particularly limited, and various glass compositions such as A-glass, C-glass, and E-glass are applied. Such glass filler may contain components such as TiO2, SO3, and P2O5 as necessary. Among these, E-glass (alkali-free glass) is more preferable. Furthermore, the plate-shaped glass filler is preferably surface-treated with a known surface treatment agent, such as a silane coupling agent, a titanate coupling agent, or an aluminate coupling agent, from the viewpoint of improving mechanical strength. Furthermore, the plate-shaped glass filler is preferably one that has been subjected to bundling treatment with an olefin-based resin, a styrene-based resin, an acrylic-based resin, a polyester-based resin, an epoxy-based resin, or a urethane-based resin. The amount of the bundling agent attached to the plate-shaped glass filler that has been subjected to bundling treatment is preferably 0.5 to 8% by weight, more preferably 1 to 4% by weight, based on 100% by weight of the plate-shaped glass filler.
[0214] Furthermore, the plate-shaped glass filler includes those that are surface-coated with different materials. Suitable examples of such different materials include metals and metal oxides. Examples of metals include silver, copper, nickel, and aluminum. Examples of metal oxides include titanium oxide, cerium oxide, zirconium oxide, iron oxide, aluminum oxide, and silicon oxide. The method of surface-coating such different materials is not particularly limited, and examples include various known plating methods (e.g., electrolytic plating, electroless plating, hot-dip plating, etc.), vacuum deposition, ion plating, CVD (e.g., thermal CVD, MOCVD, plasma CVD, etc.), PVD, and sputtering.
[0215] (E-3; Fibrous carbon filler) Examples of fibrous carbon fillers include carbon fiber, metal-coated carbon fiber, carbon milled fiber, vapor-grown carbon fiber, and carbon nanotubes. Carbon nanotubes may have a fiber diameter of 0.003 to 0.1 μm and may be single-walled, double-walled, or multi-walled, with multi-walled (so-called MWCNT) being preferred. Among these, carbon fiber and metal-coated carbon fiber are preferred because of their excellent mechanical strength and the ability to impart good electrical conductivity. Good electrical conductivity is one of the important properties required of resin materials in recent digital precision instruments (e.g., digital still cameras).
[0216] As the carbon fiber, any of cellulose-based, polyacrylonitrile-based, and pitch-based carbon fibers can be used. Also, those obtained by a method of spinning without a non-infusible step, such as a method of forming or shaping a raw material composition consisting of a polymer of methylene-type bonds of aromatic sulfonic acids or their salts and a solvent, and then carbonizing the raw material composition, can be used. Furthermore, any of general-purpose types, medium elastic modulus types, and high elastic modulus types can be used. Among these, polyacrylonitrile-based high elastic modulus types are particularly preferred. The average fiber diameter of the carbon fiber is not particularly limited, but is usually 3 to 15 μm, preferably 5 to 13 μm. Carbon fibers having an average fiber diameter in this range may be able to exhibit good mechanical strength and fatigue properties without impairing the appearance of the molded product. The preferred fiber length of the carbon fiber is 60 to 500 μm, preferably 80 to 400 μm, and particularly preferably 100 to 300 μm, as the number average fiber length in the thermoplastic resin composition. The number average fiber length is a value calculated by an image analyzer from optical microscopic observation of the carbon fiber residues collected by high-temperature incineration of molded products, dissolution with a solvent, decomposition with chemicals, etc. The value is calculated by a method that does not count fibers having a length shorter than the fiber length. The aspect ratio of the carbon fiber is preferably in the range of 10 to 200, more preferably in the range of 15 to 100, and even more preferably in the range of 20 to 50. The aspect ratio is the value obtained by dividing the average fiber length by the average fiber diameter.
[0217] Furthermore, the surface of the carbon fiber is preferably subjected to an oxidation treatment in order to increase adhesion to the matrix resin and improve mechanical strength. The oxidation treatment method is not particularly limited, but suitable examples include (1) a method of treating a fibrous carbon filler with an acid or alkali or a salt thereof, or an oxidizing gas, (2) a method of baking a fiber or a fibrous carbon filler that can be made into a fibrous carbon filler at a temperature of 700° C. or higher in the presence of an inert gas containing an oxygen-containing compound, and (3) a method of subjecting a fibrous carbon filler to an oxidation treatment and then heat treatment in the presence of an inert gas.
[0218] Metal-coated carbon fiber is a carbon fiber having a metal layer coated on its surface. Examples of metals include silver, copper, nickel, and aluminum, with nickel being preferred in terms of corrosion resistance of the metal layer. As a method for metal coating, the various methods described above for surface coating with different materials in the plate-shaped glass filler can be used. Among these, plating is preferably used. In addition, in the case of such metal-coated carbon fiber, the above-mentioned carbon fibers can be used as the original carbon fiber. The thickness of the metal coating layer is preferably 0.1 to 1 μm, more preferably 0.15 to 0.5 μm, and even more preferably 0.2 to 0.35 μm.
[0219] Such carbon fibers and metal-coated carbon fibers are preferably bundled and treated with an olefin resin, a styrene resin, an acrylic resin, a polyester resin, an epoxy resin, a urethane resin, etc. In particular, fibrous carbon fillers treated with a urethane resin or an epoxy resin are preferred in the present invention because of their excellent mechanical strength.
[0220] (E-4; Non-fibrous carbon filler) Examples of non-fibrous carbon fillers include carbon black, graphite, and fullerene. Among these, carbon black and graphite are preferred from the viewpoints of mechanical strength, wet heat resistance, and thermal stability. As carbon black, carbon black having a DBP oil absorption of 100 ml / 100 g to 500 ml / 100 g is preferred from the viewpoint of electrical conductivity. Such carbon black is generally acetylene black or ketjen black. Specific examples include Denka Black manufactured by Denki Kagaku Kogyo Co., Ltd., Vulcan XC-72 and BP-2000 manufactured by Cabot Corporation, and Ketjen Black EC and Ketjen Black EC-600JD manufactured by Lion Corporation.
[0221] As graphite, either natural graphite, known as graphite by its mineral name, or various types of artificial graphite can be used. As natural graphite, any of earthy graphite, vein graphite (also known as lump graphite), and flake graphite can be used. Artificial graphite is made by heat treating amorphous carbon to artificially orient microscopic graphite crystals in an irregular arrangement, and includes kish graphite, decomposed graphite, and pyrolytic graphite in addition to the artificial graphite used in general carbon materials. The artificial graphite used in general carbon materials is usually manufactured by graphitizing petroleum coke or coal-based pitch coke as the main raw material.
[0222] The graphite of the present invention may include expanded graphite that has been made thermally expandable by a treatment such as an acid treatment, or graphite that has been expanded. The particle size of the graphite is preferably in the range of 2 to 300 μm. The particle size is more preferably 5 to 200 μm, further preferably 7 to 100 μm, and particularly preferably 7 to 50 μm. By satisfying these ranges, good mechanical strength and molded product appearance may be achieved. On the other hand, if the average particle size is less than 2 μm, the effect of improving rigidity may be small, and if the average particle size exceeds 300 μm, the impact resistance may be significantly reduced and so-called graphite floating may become noticeable on the surface of the molded product, which is not preferable.
[0223] The graphite of the present invention has a fixed carbon content of preferably 80% by weight or more, more preferably 90% by weight or more, and even more preferably 98% by weight or more. The graphite of the present invention has a volatile content of preferably 3% by weight or less, more preferably 1.5% by weight or less, and even more preferably 1% by weight or less.
[0224] The average particle size of graphite in the present invention refers to the particle size of the graphite itself before it becomes a resin composition, and this particle size is determined by a laser diffraction / scattering method.
[0225] Furthermore, the surface of the graphite may be subjected to a surface treatment, such as an epoxy treatment, a urethane treatment, a silane coupling treatment, or an oxidation treatment, in order to increase its affinity with the thermoplastic resin, as long as the properties of the composition of the present invention are not impaired.
[0226] (E-5; Silicate minerals) The inorganic filler in the present invention includes silicate minerals consisting of at least a metal oxide component and a SiO2 component, and preferably includes orthosilicate, disilicate, cyclic silicate, chain silicate, etc. The silicate minerals are in a crystalline state, and the crystals may be in any form that each silicate mineral can have, and the crystals may have various shapes such as fibers and plates.
[0227] The silicate mineral may be any of the compounds of a complex oxide, an oxyacid salt (composed of an ion lattice), or a solid solution, and the complex oxide may be any of a combination of two or more single oxides, or a combination of two or more single oxides and oxyacid salts, and the solid solution may be any of a solid solution of two or more metal oxides, or a solid solution of two or more oxyacid salts. It may also be a hydrate. The form of the water of crystallization in the hydrate may be any of the forms that enter as hydrogen silicate ions as Si-OH, that enter ionic form as hydroxide ions (OH-) against metal cations, or that enter as H2O molecules in the gaps in the structure.
[0228] As the silicate mineral, an artificially synthesized product corresponding to a natural product can be used. As the artificially synthesized product, a silicate mineral obtained by various conventionally known methods, for example, various synthesis methods using solid reaction, hydrothermal reaction, and ultra-high pressure reaction, can be used.
[0229] Specific examples of silicate minerals in each metal oxide component include the following: The notation in parentheses indicates the name of the mineral, etc. that contains such a silicate mineral as a main component, and means that the compound in parentheses can be used as the exemplified metal salt.
[0230] Examples of rocks that contain K2O include K2O·SiO2, K2O·4SiO2·H2O, K2O·Al2O3·2SiO2 (kalsilite), K2O·Al2O3·4SiO2 (leucite), and K2O·Al2O3·6SiO2 (orthoclase).
[0231] Minerals containing Na2O as a component include Na2O·SiO2 and its hydrates, Na2O·2SiO2, 2Na2O·SiO2, Na2O·4SiO2, Na2O·3SiO2·3H2O, Na2O·Al2O3·2SiO2, Na2O·Al2O3·4SiO2 (jadeite), 2Na2O·3CaO·5SiO2, 3Na2O·2CaO·5SiO2, and Na2O·Al2O3·6SiO2 (albite).
[0232] Examples of rocks containing Li2O include Li2O·SiO2, 2Li2O·SiO2, Li2O·SiO2·H2O, 3Li2O·2SiO2, Li2O·Al2O3·4SiO2 (petalite), Li2O·Al2O3·2SiO2 (eucryptite), and Li2O·Al2O3·4SiO2 (spodumene).
[0233] Examples of stones containing BaO include BaO·SiO2, 2BaO·SiO2, BaO·Al2O3·2SiO2 (celsian), and BaO·TiO2·3SiO2 (bentite).
[0234] Materials containing CaO include tobermorite group such as 3CaO·SiO2 (alite, a cement clinker mineral), 2CaO·SiO2 (belite, a cement clinker mineral), 2CaO·MgO·2SiO2 (akermanite), 2CaO·Al2O3·SiO2 (gehlenite), a solid solution of akermanite and gehlenite (melilite), CaO·SiO2 (wollastonite (both α-type and β-type)), CaO·MgO·2SiO2 (diopside), CaO·MgO·SiO2 (magnesium olivine), 3CaO·MgO·2SiO2 (merwinite), CaO·Al2O3·2SiO2 (anorthite), 5CaO·6SiO2·5H2O (tobermorite, and others such as 5CaO·6SiO2·9H2O). loop hydrates, wollastonite group hydrates such as 2CaO·SiO2·H2O (hillebrandite), xonotlite group hydrates such as 6CaO·6SiO2·H2O (xonotlite), gyrolite group hydrates such as 2CaO·SiO2·2H2O (gyrolite), CaO·Al2O3·2SiO2·H2O (lawsonite), CaO·FeO·2SiO2 (hedengite), 3CaO·2SiO2 (chilcoanite), 3CaO·Al2O3·3SiO2 (grossula), 3CaO·Fe2O3·3SiO2 (andradite), 6CaO·4Al2O3·FeO·SiO2 (pleochroite), as well as clinozoisite, pomegranate, allanite, vesuvianite, onoite, scotite, and augite.
[0235] Portland cement can be mentioned as an example of a silicate mineral containing CaO as a component. The type of Portland cement is not particularly limited, and any type such as normal, early strength, super early strength, medium heat, sulfate resistant, white, etc. can be used. Furthermore, various types of mixed cements, such as blast furnace cement, silica cement, and fly ash cement, can be used as component B. Other examples of silicate minerals containing CaO as a component include blast furnace slag and ferrite.
[0236] Examples of compounds that contain ZnO include ZnO·SiO2, 2ZnO·SiO2 (troostite), and 4ZnO·2SiO2·H2O (hemimorphite). Examples of rocks that contain MnO include MnO·SiO2, 2MnO·SiO2, CaO·4MnO·5SiO2 (rhodonite) and coesrite. Examples of rocks containing FeO include FeO·SiO2 (ferrosilite), 2FeO·SiO2 (ferroolitic olivine), 3FeO·Al2O3·3SiO2 (almandine), and 2CaO·5FeO·8SiO2·H2O (tetractinocene).
[0237] Examples of materials that contain CoO include CoO·SiO2 and 2CoO·SiO2.
[0238] Materials containing MgO include MgO·SiO2 (steatite, enstatite), 2MgO·SiO2 (forsterite), 3MgO·Al2O3·3SiO2 (byrope), 2MgO·2Al2O3·5SiO2 (cordierite), 2MgO·3SiO2·5H2O, 3MgO·4SiO2·H2O (talc), 5MgO·8SiO2·9H2O (attapulgite), 4M 5MgO·Al2O3·3SiO2·4H2O (chlorite), K2O·6MgO·Al2O3·6SiO2·2H2O (phlogovite), Na2O·3MgO·3Al2O3·8SiO2·H2O (lanthanite), and magnesium tourmaline, Examples include orthoclase, cummingtonite, vermiculite, and smectite.
[0239] Examples of materials that contain Fe2O3 include Fe2O3·SiO2.
[0240] Examples of refractories that contain ZrO2 include ZrO2·SiO2 (zircon) and AZS refractories.
[0241] Examples of minerals containing Al2O3 include Al2O3·SiO2 (sillimanite, andalusite, kyanite), 2Al2O3·SiO2, Al2O3·3SiO2, 3Al2O3·2SiO2 (mullite), Al2O3·2SiO2·2H2O (kaolinite), Al2O3·4SiO2·H2O (pyrophyllite), Al2O3·4SiO2·H2O (bentonite), K2O·3Na2O·4Al2O3·8SiO2 (nepheline), K2O·3Al2O3·6SiO2·2H2O (muscovite, sericite), K2O·6MgO·Al2O3·6SiO2·2H2O (phlogovite), as well as various zeolites, fluorphlogopite, and biotite.
[0242] Among the above silicate minerals, talc, mica and wollastonite are particularly preferred because they have an excellent balance between rigidity and impact resistance, are excellent in moist heat resistance, thermal stability and appearance, and are also easily available.
[0243] (E-5-i) Talc Talc is a hydrous magnesium silicate in terms of chemical composition, generally represented by the chemical formula 4SiO2·3MgO·2H2O, and is usually a scaly particle with a layered structure. It is composed of 56-65% by weight of SiO2, 28-35% by weight of MgO, and about 5% by weight of H2O. Other minor components include 0.03-1.2% by weight of Fe2O3, 0.05-1.5% by weight of Al2O3, 0.05-1.2% by weight of CaO, 0.2% by weight or less of K2O, and 0.2% by weight or less of Na2O. A more preferable composition of talc is 62-63.5% by weight of SiO2, 31-32.5% by weight of MgO, 0.03-0.15% by weight of Fe2O3, 0.05-0.25% by weight of Al2O3, and 0.05-0.25% by weight of CaO. Further, it is preferable that the ignition loss is 2 to 5.5% by weight. In such a preferable composition, a resin composition having good thermal stability and color can be obtained, and good molded products can be produced even when the molding temperature is further increased. This allows the composition of the present invention to have a higher fluidity and can be used for larger or more complex thin-walled molded products.
[0244] The particle size of the talc is preferably in the range of 0.1 to 50 μm (more preferably 0.1 to 10 μm, even more preferably 0.2 to 5 μm, and particularly preferably 0.2 to 3.5 μm) in terms of average particle size measured by a sedimentation method. Therefore, a more suitable talc of the present invention is one having the above-mentioned preferred composition and an average particle size of 0.2 to 3.5 μm. Furthermore, the bulk density is preferably 0.5 (g / cm 3 It is particularly preferable to use talc having a particle size of 0.1 mm or more as the raw material. An example of talc that satisfies these conditions is "Upn HS-T0.8" manufactured by Hayashi Kasei Co., Ltd. The average particle size of talc refers to D50 (median size of particle size distribution) measured by X-ray transmission method, which is one of the liquid phase precipitation methods. A specific example of an apparatus for performing such measurements is Sedigraph5100 manufactured by Micromeritics Co., Ltd.
[0245] There is no particular restriction on the method for pulverizing talc from raw ore, and axial flow milling, annular milling, roll milling, ball milling, jet milling, container rotation type compression shear milling, etc. can be used. Furthermore, the talc after pulverization is preferably classified using various classifiers, and one with a uniform particle size distribution is preferable. There is no particular restriction on the classifier, and impactor-type inertial force classifiers (variable impactors, etc.), Coanda effect type Examples of the classifier include inertial classifiers (such as Elbow Jet), centrifugal field classifiers (such as multi-stage cyclone, Microplex, Dispersion Separator, AccuCut, Turbo Classifier, Turboplex, Micron Separator, and Super Separator).
[0246] Furthermore, the talc is preferably in an aggregated state from the viewpoint of ease of handling, etc., and methods for producing the talc include a method using degassing compression, a method using a sizing agent for compression, etc. In particular, the method using degassing compression is preferred from the viewpoints of simplicity and of not mixing unnecessary sizing agent resin components into the resin composition of the present invention.
[0247] (E-5-ii) Mica Mica having an average particle size of 5 to 250 μm is preferably used. More preferably, the average particle size (D50 (median diameter of particle size distribution)) measured by the laser diffraction / scattering method is 5 to 50 μm. If the average particle size of the mica is less than 5 μm, it is difficult to obtain the effect of improving rigidity. On the other hand, a resin composition containing mica with an average particle size exceeding 250 μm may have poor appearance and flame retardancy while mechanical properties tend to saturate. The average particle size of the mica is measured by the laser diffraction / scattering method or the vibrating sieving method. The laser diffraction / scattering method is preferably performed on mica having a 325 mesh pass by the vibrating sieving method and 95% by weight or more. For mica with a particle size larger than this, the vibrating sieving method is generally used. In the vibrating sieving method of the present invention, first, 100 g of mica powder to be used is sieved for 10 minutes using a vibrating sieve with JIS standard sieves stacked in order of mesh size, and the weight of the powder remaining on each sieve is measured to determine the particle size distribution.
[0248] The thickness of the mica is preferably 0.01 to 1 μm as measured by observation with an electron microscope. More preferably, the thickness is 0.03 to 0.3 μm. The aspect ratio is preferably 5 to 200, more preferably 10 to 100. The mica used is preferably muscovite mica, whose Mohs hardness is about 3. Muscovite mica can achieve higher rigidity and strength than other micas such as phlogovite, and solves the problem of the present invention at a better level. Therefore, the more suitable mica of the present invention is muscovite with an average particle size of 5 to 250 μm, more preferably 5 to 50 μm. An example of such a suitable mica is "A-21" manufactured by Yamaguchi Mica Co., Ltd. The mica may be produced by either a dry grinding method or a wet grinding method as a grinding method. Dry grinding is more common and less expensive, while wet grinding is more effective for grinding mica into thinner, finer particles (which improves the rigidity of the resin composition). In the present invention, mica produced by the wet grinding method is more suitable.
[0249] (E-5-iii) Wollastonite The fiber diameter of wollastonite is preferably 0.1 to 10 μm, more preferably 0.1 to 5 μm, and even more preferably 0.1 to 3 μm. The aspect ratio (average fiber length / average fiber diameter) is preferably 3 or more. The upper limit of the aspect ratio is 30 or less. Here, the fiber diameter is measured by observing the reinforcing filler with an electron microscope, determining the individual fiber diameters, and calculating the number average fiber diameter from the measured values. The electron microscope is used because it is difficult to accurately measure the size of the target level with an optical microscope. The fiber diameter is measured by randomly extracting the filler to be measured for the image obtained by observation with the electron microscope, measuring the fiber diameter near the center, and calculating the number average fiber diameter from the measured values. The magnification of the observation is about 1000 times, and the number of measured fibers is 500 or more (600 or less is suitable for work). On the other hand, the average fiber length is measured by observing the filler with an optical microscope, determining the individual lengths, and calculating the number average fiber length from the measured values. Observation with an optical microscope begins with preparing a sample in which the fillers are dispersed so that they do not overlap too much. Observation is performed with a 20x objective lens, and the observed image is captured as image data by a CCD camera with approximately 250,000 pixels. The image data is analyzed by an image analyzer, and the fiber length is calculated using a program that determines the maximum distance between two points on the image data. Under such conditions, the size per pixel corresponds to a length of 1.25 μm, and the number of measurements is 500 or more (600 or less is preferable for work). In order to fully reflect the inherent whiteness of wollastonite in the resin composition, it is preferable to remove as much iron mixed in the raw ore and iron mixed in due to wear of the equipment when the raw ore is crushed by a magnetic separator as possible. It is preferable that the iron content in the wollastonite after such magnetic separator treatment is 0.5% by weight or less in terms of Fe2O3. Therefore, the more preferable wollastonite of the present invention is wollastonite whose fiber diameter is 0.1 to 10 μm, more preferably 0.1 to 5 μm, and even more preferably 0.1 to 3 μm, whose average particle size is 5 to 250 μm, more preferably 5 to 50 μm, and whose iron content is 0.5% by weight or less in terms of Fe2O3. Examples of suitable wollastonite include "SH-1250" and "SH-1800" manufactured by Kinsei Matec Co., Ltd., "KGP-H40" manufactured by Kansai Matec Co., Ltd., and "NYGLOS4" manufactured by NYCO Corporation.
[0250] The silicate mineral is preferably not surface-treated, but may be surface-treated with various surface treatment agents such as silane coupling agents (including alkylalkoxysilanes and polyorganohydrogensiloxanes), higher fatty acid esters, acid compounds (e.g., phosphorous acid, phosphoric acid, carboxylic acid, and carboxylic acid anhydrides), and waxes. Furthermore, the silicate mineral may be granulated with a bundling agent such as various resins, higher fatty acid esters, and waxes to form granules. Particularly suitable silicate minerals in the present invention are talc and wollastonite. Such talc and wollastonite are good in terms of both rigidity and impact resistance, and when mixed with a polycarbonate resin, the deterioration of color and appearance (e.g., the occurrence of silver streaks) is small.
[0251] The content of component E is preferably 1 to 2500 parts by weight, more preferably 50 to 2200 parts by weight, and even more preferably 100 to 2000 parts by weight, relative to 100 parts by weight of component A. If the content is less than 1 part by weight, the product strength may be insufficient, whereas if it exceeds 2500 parts by weight, strand processability may be poor and good pellets may not be obtained.
[0252] (Other additives) In the polycarbonate resin composition of the present invention, various stabilizers for preventing a decrease in molecular weight during molding and for stabilizing color tone, release agents, colorants, impact modifiers, etc. may be used.
[0253] (i) Stabilizers The polycarbonate resin composition of the present invention may contain various known stabilizers, such as phosphorus-based stabilizers, hindered phenol-based antioxidants, ultraviolet absorbers, and light stabilizers.
[0254] (i-1) Phosphorus-based stabilizers Examples of phosphorus stabilizers include phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid and their esters, and tertiary phosphines.Among these, phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid, triorganophosphate compounds, and acid phosphate compounds are particularly preferred.The organic group in the acid phosphate compound includes both mono-substitution, di-substitution, and mixtures thereof.The following exemplary compounds corresponding to the compound also include both.
[0255] Examples of the triorganophosphate compound include trimethyl phosphate, triethyl phosphate, tributyl phosphate, trioctyl phosphate, tridecyl phosphate, tridodecyl phosphate, trilauryl phosphate, tristearyl phosphate, tricresyl phosphate, triphenyl phosphate, and trichlorophenyl phosphate. Examples of the trialkyl phosphate include diphenyl cresyl phosphate, diphenyl monoorthoxenyl phosphate, and tributoxyethyl phosphate. Among these, trialkyl phosphate is preferred. The number of carbon atoms of such trialkyl phosphate is preferably 1 to 22, more preferably 1 to 4. The particularly preferred trialkyl phosphate is trimethyl phosphate.
[0256] Examples of acid phosphate compounds include methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, butoxyethyl acid phosphate, octyl acid phosphate, decyl acid phosphate, lauryl acid phosphate, stearyl acid phosphate, oleyl acid phosphate, behenyl acid phosphate, phenyl acid phosphate, nonylphenyl acid phosphate, cyclohexyl acid phosphate, phenoxyethyl acid phosphate, alkoxypolyethylene glycol acid phosphate, and bisphenol A acid phosphate. Among these, long-chain dialkyl acid phosphates having 10 or more carbon atoms are preferred because they are effective in improving thermal stability and the acid phosphate itself is highly stable.
[0257] Examples of the phosphite compound include triphenyl phosphite, tris(nonylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, tris(diethylphenyl)phosphite, tris(di-iso-propylphenyl)phosphite, tris(di-n-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, tris(2,6-di-tert-butylphenyl)phosphite, phenyl)phosphite, distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-ethylphenyl)pentaerythritol diphosphite, bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, and dicyclohexyl pentaerythritol diphosphite.
[0258] Other phosphite compounds that react with dihydric phenols to form a cyclic structure can also be used, such as 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octylphosphite.
[0259] Examples of the phosphonite compounds include tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, bis(2,4-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, and bis(2,4-di-tert-butylphenyl)-3-phenyl-phenylphosphonite. Examples of the phosphonite include bis(2,6-di-n-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, and bis(2,6-di-tert-butylphenyl)-3-phenyl-phenylphosphonite, and tetrakis(di-tert-butylphenyl)-biphenylene diphosphonite and bis(di-tert-butylphenyl)-phenyl-phenylphosphonite are preferred, and tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite and bis(2,4-di-tert-butylphenyl)-phenyl-phenylphosphonite are more preferred. Such phosphonite compounds can be used in combination with the phosphite compounds having an aryl group substituted with two or more alkyl groups, and are therefore preferred.
[0260] Examples of the phosphonate compound include dimethyl benzenephosphonate, diethyl benzenephosphonate, and dipropyl benzenephosphonate.
[0261] Examples of tertiary phosphines include triethylphosphine, tripropylphosphine, tributylphosphine, trioctylphosphine, triamylphosphine, dimethylphenylphosphine, dibutylphenylphosphine, diphenylmethylphosphine, diphenyloctylphosphine, triphenylphosphine, tri-p-tolylphosphine, trinaphthylphosphine, and diphenylbenzylphosphine. A particularly preferred tertiary phosphine is triphenylphosphine.
[0262] Suitable phosphorus-based stabilizers are triorganophosphate compounds, acid phosphate compounds, and phosphite compounds represented by the following general formula (24). It is particularly preferable to use a triorganophosphate compound.
[0263] [ka]
[0264] (In the above general formula (24), R and R' represent an alkyl group having 6 to 30 carbon atoms or an aryl group having 6 to 30 carbon atoms, and may be the same or different.)
[0265] As described above, the phosphonite compound is preferably tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite, and stabilizers containing this phosphonite as a main component are commercially available as Sandostab P-EPQ (trademark, manufactured by Clariant) and Irgafos P-EPQ (trademark, manufactured by CIBA SPECIALTY CHEMICALS), either of which can be used.
[0266] Among the phosphite compounds of the above formula (24), more preferred ones are distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, and bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite.
[0267] (i-2) Hindered phenol antioxidants As the hindered phenol compound, various compounds that are usually blended in resins can be used. Examples of such hindered phenol compounds include α-tocopherol, butyl Hydroxytoluene, sinapyl alcohol, vitamin E, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenylacrylate, 2,6-di-tert-butyl-4-(N,N-dimethylaminomethyl)phenol, 3,5-di-tert-butyl-4-hydroxybenzylphosphonate diethyl ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol) 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-dimethylenebis(6-α-methyl-benzyl-p-cresol), 2,2'-ethylidenebis(4,6-di-tert-butylphenol), 2,2'-butylidenebis(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol) 1,6-Hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis[2-tert-butyl-4-methyl 6-(3-tert-butyl-5-methyl-2-hydroxybenzyl)phenyl]terephthalate, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1,-dimethylethyl}-2 ,4,8,10-Tetraoxaspiro[5,5]undecane, 4,4'-thiobis(6-tert-butyl-m-cresol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), bis(3,5-di-tert-butyl-4-hydroxybenzyl)sulfide, 4,4'-di-thiobis(2,6-di-tert-butylphenol), 4,4'-tri-thiobis(2,6-di-tert-butylphenol), 2,2-thiodiethylenebis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, N,N'-hexamethylenebis-(3,5-di-tert-butyl-4-hydroxyhydrocinnamide), N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butyl 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydroxyphenyl)isocyanurate, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanurate, 1,3,5-tris2[3(3,5-di-tert-butyl-4-hydroxyphenyl)isocyanurate, hydroxyphenyl)propionyloxy]ethyl isocyanurate, tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acetate, 3,9-bis[2-{3-(3-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl isocyanurate Examples include tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, 1,3,5-trimethyl-2,4,6-tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)benzene, and tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)isocyanurate.
[0268] Among the above compounds, in the present invention, tetrakis[methylene-3-(3-tert- butyl-4-hydroxy-5-methylphenyl)propionate]methane, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane are preferably used. In particular, 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane is preferred. The above hindered phenol-based antioxidants can be used alone or in combination of two or more kinds.
[0269] It is preferable to use either a phosphorus-based stabilizer or a hindered phenol-based antioxidant. It is particularly preferable to use a phosphorus-based stabilizer, and it is more preferable to use a triorganophosphate compound. The content of the phosphorus-based stabilizer and the hindered phenol-based antioxidant is preferably 0.005 to 5 parts by weight, more preferably 0.1 to 4 parts by weight, per 100 parts by weight of component A.
[0270] (i-3) Ultraviolet absorbers The polycarbonate resin composition of the present invention may contain an ultraviolet absorber. Since the polycarbonate resin composition of the present invention has a good hue, the incorporation of an ultraviolet absorber can maintain the hue for a long period of time even when used outdoors.
[0271] Benzophenones include, for example, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxytrihydridolate benzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sodium sulfoxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone.
[0272] Benzotriazoles include, for example, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, Examples of the polymer include polymers having a 2-hydroxyphenyl-2H-benzotriazole skeleton, such as azole, 2-(2-hydroxy-5-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-4-octoxyphenyl)benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), 2,2'-p-phenylenebis(1,3-benzoxazin-4-one), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole, as well as copolymers of 2-(2'-hydroxy-5-methacryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer, and copolymers of 2-(2'-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer.
[0273] Examples of hydroxyphenyl triazines include 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-methyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-ethyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-propyloxyphenol, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-butyloxyphenol.Further examples include compounds in which the phenyl group of the above-mentioned compounds is replaced with a 2,4-dimethylphenyl group, such as 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hexyloxyphenol.
[0274] Examples of cyclic imino esters include 2,2'-p-phenylenebis(3,1-benzoxazin-4-one), 2,2'-(4,4'-diphenylene)bis(3,1-benzoxazin-4-one), and 2,2'-(2,6-naphthalene)bis(3,1-benzoxazin-4-one).
[0275] Specific examples of ultraviolet absorbers include cyanoacrylate-based agents such as 1,3-bis-[(2'-cyano-3',3'-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl)propane and 1,3-bis-[(2-cyano-3,3-diphenylacryloyl)oxy]benzene.
[0276] Furthermore, the ultraviolet absorber may be a polymer type ultraviolet absorber obtained by copolymerizing such an ultraviolet absorbing monomer and / or a light stable monomer having a hindered amine structure with a monomer such as an alkyl (meth)acrylate by adopting a structure of a radically polymerizable monomer compound. Suitable examples of the ultraviolet absorbing monomer include compounds containing a benzotriazole skeleton, a benzophenone skeleton, a triazine skeleton, a cyclic imino ester skeleton, and a cyanoacrylate skeleton in the ester substituent of a (meth)acrylic acid ester.
[0277] Among the above, benzotriazole-based and hydroxyphenyltriazine-based are preferred from the viewpoint of ultraviolet absorbing ability, and cyclic imino ester-based and cyanoacrylate-based are preferred from the viewpoint of heat resistance and color. The above ultraviolet absorbing agents may be used alone or in a mixture of two or more kinds.
[0278] The content of the ultraviolet absorber is preferably 0.1 to 100 parts by weight, more preferably 0.2 to 80 parts by weight, still more preferably 0.5 to 70 parts by weight, and most preferably 1 to 60 parts by weight, relative to 100 parts by weight of the A component.
[0279] (i-4) Other heat stabilizers The polycarbonate resin composition of the present invention may also contain other heat stabilizers in addition to the above phosphorus-based stabilizers and hindered phenol-based antioxidants. Such other heat stabilizers are preferably used in combination with either one of these stabilizers and antioxidants, and are particularly preferably used in combination with both. Examples of such other heat stabilizers include lactone-based stabilizers, such as the reaction product of 3-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene (details of such stabilizers are described in JP-A-7-233160). A suitable example of such a compound is Irganox HP-136 (trademark, manufactured by CIBA SPECIALTY CHEMICALS), which is commercially available and can be used. Furthermore, stabilizers in which the compound is mixed with various phosphite compounds and hindered phenol compounds are commercially available. A suitable example is Irganox HP-2921 manufactured by the above company. In the present invention, such premixed stabilizers can also be used. The content of the lactone stabilizer is preferably 0.0005 to 0.05 parts by weight, more preferably 0.001 to 0.03 parts by weight, based on 100 parts by weight of component A.
[0280] Other examples of the stabilizer include sulfur-containing stabilizers such as pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-laurylthiopropionate), and glycerol-3-stearylthiopropionate. Such stabilizers are particularly effective when the polycarbonate resin composition is applied to rotational molding. The amount of such sulfur-containing stabilizers is preferably 0.01 to 5 parts by weight, more preferably 0.1 to 2 parts by weight, based on 100 parts by weight of component A.
[0281] (ii) Release agent The polycarbonate resin composition of the present invention may further contain known release agents such as fatty acid esters, polyolefin waxes, silicone compounds, fluorine compounds (fluorine oils such as polyfluoroalkyl ethers), paraffin wax, and beeswax, in order to improve the productivity during molding and the dimensional accuracy of the molded product. The polycarbonate resin composition of the present invention has good fluidity, so that a molded product with good pressure transmission and uniform distortion can be obtained. On the other hand, in the case of a molded product with a complex shape that has a large mold release resistance, there is a risk of deformation of the molded product during mold release. The incorporation of the above specific components solves this problem without impairing the properties of the polycarbonate resin composition.
[0282] Such fatty acid ester is an ester of an aliphatic alcohol and an aliphatic carboxylic acid. Such aliphatic alcohol may be a monohydric alcohol or a polyhydric alcohol having dihydric or more. The carbon number of the alcohol is preferably 3 to 32, more preferably 5 to 30. On the other hand, the aliphatic carboxylic acid is preferably an aliphatic carboxylic acid having 3 to 32 carbon atoms, more preferably 10 to 30 carbon atoms. Among them, saturated aliphatic carboxylic acids are preferred. The fatty acid ester of the present invention is preferred in that the full ester has excellent thermal stability at high temperatures. The acid value of the fatty acid ester of the present invention is preferably 20 or less (can be substantially 0). The hydroxyl value of the fatty acid ester is more preferably in the range of 0.1 to 30. Furthermore, the iodine value of the fatty acid ester is preferably 10 or less (can be substantially 0). These properties can be determined by the method specified in JIS K 0070.
[0283] Examples of polyolefin waxes include ethylene homopolymers, homopolymers or copolymers of α-olefins having 3 to 60 carbon atoms, or copolymers of ethylene and α-olefins having 3 to 60 carbon atoms, each having a molecular weight of 1,000 to 10,000. The molecular weight is a number average molecular weight measured in terms of standard polystyrene by GPC (gel permeation chromatography). The upper limit of the number average molecular weight is more preferably 6,000, and even more preferably 3,000. The carbon number of the α-olefin component in the polyolefin wax is preferably 60 or less, more preferably 40 or less. More preferred examples include propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. A preferred polyolefin wax is an ethylene homopolymer, or a copolymer of ethylene and α-olefins having 3 to 60 carbon atoms. The proportion of the α-olefins having 3 to 60 carbon atoms is preferably 20 mol% or less, more preferably 10 mol% or less. A commercially available polyethylene wax is preferably used.
[0284] The content of the release agent is preferably 0.05 to 15 parts by weight, more preferably 0.1 to 12 parts by weight, and further preferably 0.5 to 10 parts by weight, based on 100 parts by weight of the A component.
[0285] (iii) Dyes and pigments The polycarbonate resin composition of the present invention further contains various dyes and pigments, and can provide molded products that exhibit a variety of designs. Examples of dyes and pigments used in the present invention include perylene dyes, coumarin dyes, thioindigo dyes, anthraquinone dyes, thioxanthone dyes, ferrocyanides such as Prussian blue, perinone dyes, quinoline dyes, quinacridone dyes, dioxazine dyes, isoindolinone dyes, and phthalocyanine dyes. Furthermore, the polycarbonate resin composition of the present invention can be blended with a metallic pigment to obtain a better metallic color. Aluminum powder is suitable as the metallic pigment. In addition, by blending a fluorescent brightener or other fluorescent dye that emits light, a better design effect that makes use of the luminous color can be imparted.
[0286] Examples of the fluorescent dyes (including fluorescent whitening agents) used in the present invention include coumarin-based fluorescent dyes, benzopyran-based fluorescent dyes, perylene-based fluorescent dyes, anthraquinone-based fluorescent dyes, thioindigo-based fluorescent dyes, xanthene-based fluorescent dyes, xanthone-based fluorescent dyes, thioxanthene-based fluorescent dyes, thioxanthone-based fluorescent dyes, thiazine-based fluorescent dyes, and diaminostilbene-based fluorescent dyes. Among these, coumarin-based fluorescent dyes, benzopyran-based fluorescent dyes, and perylene-based fluorescent dyes are preferred because they have good heat resistance and are less likely to deteriorate during molding of polycarbonate resin.
[0287] The content of the dye or pigment is preferably from 0.00001 to 10 parts by weight, and more preferably from 0.00005 to 8 parts by weight, relative to 100 parts by weight of the A component.
[0288] (iv) Compounds capable of absorbing heat rays The polycarbonate resin composition of the present invention may contain a compound having heat absorbing ability. Suitable examples of such compounds include phthalocyanine-based near infrared absorbing agents, metal oxide-based near infrared absorbing agents such as ATO, ITO, iridium oxide, ruthenium oxide, and immonium oxide, various metal compounds having excellent near infrared absorbing ability such as metal boride-based and tungsten oxide-based near infrared absorbing agents such as lanthanum boride, cerium boride, and tungsten boride, and carbon fillers. As such phthalocyanine-based near infrared absorbing agents, for example, MIR-362 manufactured by Mitsui Chemicals, Inc. is commercially available and easily available. Examples of carbon fillers include carbon black, graphite (both natural and artificial), and fullerene, and preferably carbon black and graphite. These can be used alone or in combination of two or more. The content of the phthalocyanine-based near infrared absorbing agent is preferably 0.0005 to 1 part by weight, more preferably 0.0008 to 0.8 parts by weight, and even more preferably 0.001 to 0.7 parts by weight, relative to 100 parts by weight of component A. The contents of the metal oxide-based near infrared absorbing agent, metal boride-based near infrared absorbing agent, and carbon filler in the resin composition of the present invention are preferably in the range of 0.1 to 200 ppm (weight ratio), and more preferably in the range of 0.5 to 100 ppm.
[0289] (v) Light diffusing agent The polycarbonate resin composition of the present invention can be blended with a light diffusing agent to impart a light diffusing effect. Examples of such light diffusing agents include polymer fine particles, inorganic fine particles with a low refractive index such as calcium carbonate, and composites thereof. Such polymer fine particles are fine particles already known as light diffusing agents for polycarbonate resins. More preferred examples include acrylic crosslinked particles with a particle size of several μm and silicone crosslinked particles represented by polyorganosilsesquioxane. Examples of the shape of the light diffusing agent include spherical, discoid, columnar, and indefinite shapes. Such spheres do not need to be perfect spheres and include deformed ones, and such columnar shapes include cubes. A preferred light diffusing agent is spherical, and the more uniform the particle size, the more preferred it is. The content of the light diffusing agent is preferably 0.05 to 400 parts by weight, more preferably 0.1 to 300 parts by weight, and even more preferably 0.5 to 200 parts by weight, relative to 100 parts by weight of component A. Two or more types of light diffusing agents can be used in combination.
[0290] (vi) Highly light-reflecting white pigments The polycarbonate resin composition of the present invention can be blended with a highly light-reflecting white pigment to impart a light-reflecting effect. Titanium dioxide (particularly titanium dioxide treated with an organic surface treatment agent such as silicone) pigment is particularly preferred as such a white pigment. The content of such highly light-reflecting white pigment is preferably 1 to 500 parts by weight, more preferably 5 to 300 parts by weight, per 100 parts by weight of component A. Two or more types of highly light-reflecting white pigments can be used in combination.
[0291] (vii) Antistatic agents The polycarbonate resin composition of the present invention may be required to have antistatic properties, and in such a case, it is preferable to include an antistatic agent. Examples of such antistatic agents include (1) arylsulfonic acid phosphonium salts, such as dodecylbenzenesulfonic acid phosphonium salts, and organic sulfonic acid phosphonium salts, such as alkylsulfonic acid phosphonium salts, and boric acid phosphonium salts, such as tetrafluoroborate phosphonium salts. The content of the phosphonium salt is appropriately 100 parts by weight or less, preferably 0.05 to 100 parts by weight, more preferably 1 to 80 parts by weight, and even more preferably 1.5 to 70 parts by weight, relative to 100 parts by weight of component A.
[0292] Examples of the antistatic agent include (2) organic sulfonate alkali (earth) metal salts such as lithium organic sulfonate, sodium organic sulfonate, potassium organic sulfonate, cesium organic sulfonate, rubidium organic sulfonate, calcium organic sulfonate, magnesium organic sulfonate, and barium organic sulfonate. As mentioned above, such metal salts are also used as flame retardants. More specifically, such metal salts include metal salts of dodecylbenzenesulfonic acid and metal salts of perfluoroalkanesulfonic acid. The content of the organic sulfonate alkali (earth) metal salt is suitably 20 parts by weight or less, preferably 0.01 to 20 parts by weight, and more preferably 0.05 to 10 parts by weight, relative to 100 parts by weight of component A. In particular, alkali metal salts such as potassium, cesium, and rubidium are suitable.
[0293] Examples of the antistatic agent include (3) organic ammonium sulfonate salts such as ammonium alkylsulfonate salts and ammonium arylsulfonate salts. The amount of the ammonium salts is preferably 2 parts by weight or less based on 100 parts by weight of the total of components A, B, and C. Examples of the antistatic agent include (4) polymers containing a poly(oxyalkylene) glycol component as a constituent component, such as polyether ester amide. The amount of the polymer is preferably 100 parts by weight or less based on 100 parts by weight of component A.
[0294] (viii) Other additives The polycarbonate resin composition of the present invention can be blended with thermoplastic resins other than the A and B components, elastomers, other flow modifiers, antibacterial agents, dispersants such as liquid paraffin, photocatalytic antifouling agents and photochromic agents, ionic liquids, and the like.
[0295] Examples of such other resins include polyamide resins, polyimide resins, polyetherimide resins, polyurethane resins, silicone resins, polyphenylene ether resins, polyphenylene sulfide resins, polysulfone resins, polyolefin resins such as polyethylene and polypropylene, polystyrene resins, acrylonitrile / styrene copolymers (AS resins), acrylonitrile / butadiene / styrene copolymers (ABS resins), and polymethacrylate resins. Examples of the resin include phenol resin, epoxy resin, cyclic polyolefin resin, polylactic acid resin, polycaprolactone resin, and thermoplastic fluorine resin (typified by, for example, polyvinylidene fluoride resin).
[0296] Examples of the elastomer include isobutylene / isoprene rubber, styrene / butadiene rubber, ethylene / propylene rubber, acrylic elastomers, polyester elastomers, polyamide elastomers, and core-shell elastomers such as MBS (methyl methacrylate / styrene / butadiene) rubber and MAS (methyl methacrylate / acrylonitrile / styrene) rubber. The content of the other thermoplastic resin is preferably 4000 parts by weight or less, more preferably 3000 parts by weight or less, per 100 parts by weight of component A.
[0297] (Method for producing polycarbonate resin composition) The method for producing the polycarbonate resin composition of the present invention is not particularly limited, and any known method can be used. For example, the A component, B component, C component, D component, E component, and any other additives are thoroughly mixed using a premixing means such as a V-type blender, a Henschel mixer, a mechanochemical device, or an extrusion mixer, and then the premix is granulated as necessary using an extrusion granulator or a briquetting machine, and then melt-kneaded using a melt kneader such as a vented twin-screw extruder, and then pelletized using a pelletizer.
[0298] Other examples include a method of independently supplying each component to a melt kneader, such as a vented twin-screw extruder, a method of supplying to a melt kneader using a supercritical fluid, and a method of premixing a part of each component and then supplying to a melt kneader independently of the remaining components. Examples of a method of premixing a part of each component include a method of premixing components other than component A in advance and then mixing them with component A or supplying them directly to an extruder. Examples of a method of premixing include a method in which, when component A includes a powder-form component, a part of the powder is blended with the additive to be mixed to produce a master batch of additives diluted with the powder, and the master batch is used. Further examples include a method of independently supplying one component from the middle of a melt extruder. In addition, when the components to be mixed are liquid, a so-called liquid injection device or liquid addition device can be used to supply to the melt extruder.
[0299] The extruder preferably has a vent capable of degassing moisture in the raw materials and volatile gases generated from the melt-kneaded resin. A vacuum pump is preferably installed from the vent to efficiently discharge the generated moisture and volatile gases to the outside of the extruder. It is also possible to install a screen in a zone before the extruder die section to remove foreign matter mixed in the extrusion raw materials, thereby removing the foreign matter from the resin composition. Examples of such a screen include a wire mesh, a screen changer, and a sintered metal plate (such as a disk filter).
[0300] Examples of the melt kneader include a twin-screw extruder, a Banbury mixer, a kneading roll, a single-screw extruder, and a multi-screw extruder having three or more screws.
[0301] The resin extruded as described above is directly cut and pelletized, or strands are formed and then the strands are cut by a pelletizer and pelletized. When it is necessary to reduce the influence of external dust during pelletization, it is preferable to purify the atmosphere around the extruder. Furthermore, in the production of such pellets, various methods already proposed for polycarbonate resins for optical disks can be used to appropriately narrow the shape distribution of the pellets, reduce miscuts, reduce fine powder generated during transportation or shipping, and reduce bubbles (vacuum bubbles) generated inside the strands or pellets. These prescriptions can achieve high cycle molding and reduce the rate of defects such as silver. The shape of the pellets can be a general shape such as a cylinder, a rectangular column, or a sphere, but is more preferably a cylinder. The diameter of such a cylinder is preferably 1 to 5 mm, more preferably 1.5 to 4 mm, and even more preferably 2 to 3.3 mm. On the other hand, the length of the cylinder is preferably 1 to 30 mm, more preferably 2 to 5 mm, and even more preferably 2.5 to 3.5 mm.
[0302] The polycarbonate resin composition of the present invention can be used to produce various products by injection molding the pellets produced as described above to obtain molded products. In such injection molding, not only conventional molding methods but also injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including a method of injecting a supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, sandwich molding, and ultra-high speed injection molding can be used. In addition, molding can be performed using either a cold runner system or a hot runner system.
[0303] The polycarbonate resin composition of the present invention can also be used in the form of various profile extrusion molded products, sheets, films, etc. by extrusion molding. For molding sheets and films, inflation methods, calendar methods, casting methods, etc. can also be used. Furthermore, it can be molded into heat shrinkable tubes by subjecting the composition to a specific stretching operation. The polycarbonate resin composition of the present invention can also be molded into molded products by rotational molding, blow molding, etc. Effect of the Invention
[0304] The resin composition of the present invention, which is composed of an aromatic polycarbonate resin, a circuit formation stabilizer, a flame retardant and a fluorine-containing drip prevention agent, has strength, appearance, flame retardancy, low dielectric properties, as well as good adhesion to metal thin films during circuit formation and long-term durability, and can therefore be suitably used as a wideband antenna in buildings, building materials, agricultural materials, marine materials, vehicles, electrical and electronic equipment, machinery and other various fields, and as a three-dimensional design material for said antenna in electronic equipment. Therefore, the industrial effects of the present invention are extremely great. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0305] The embodiments of the present invention are those that summarize the preferred ranges of the above-mentioned requirements, and representative examples are described in the following examples, although the present invention is not limited to these embodiments. EXAMPLES
[0306] Examples and Comparative Examples of the present invention will now be described in detail, but the present invention is not limited thereto. The measurement items in the examples were measured by the following methods.
[0307] 1. Evaluation of aromatic polycarbonate resin (i) Viscosity average molecular weight (Mv) The specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of aromatic polycarbonate resin dissolved in 100 ml of methylene chloride. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] The specific viscosity (η SP ) and the viscosity average molecular weight Mv was calculated using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 Mv 0.83 c=0.7
[0308] 2. Evaluation of resin composition (i) Impact properties (Charpy impact value) (with notch) Measurements were carried out in accordance with ISO179 (measurement conditions: 23°C) using test pieces with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm obtained by the method described below. (ii) Surface appearance The surface appearance of the molding material obtained by the method described below was visually observed. Those in which no defects in appearance due to insufficient dispersibility of component C were found were rated as ○ (good), those in which defects were found partially were rated as △ (fairly good), and those in which defects were found over the entire surface of the molded article were rated × (bad). (iii) Dielectric properties Using a test piece of 300 mm length x 300 mm width x 1 mm thickness obtained by the method described below, a 20 cm long microstrap line was made by etching, and the radio wave permeability at 10 GHz was measured using a vector network analyzer. The higher this value, the lower the dielectric properties. (iV) Adhesion Plate-shaped test pieces of 50 mm length x 100 mm width x 1 mm thickness obtained by the method described below were plated under the conditions described below, and then the adhesion between the metal thin film and the resin was evaluated. The cross-cut peel test was performed in accordance with 4-6 of "JISK5600 General Test Method for Paints." ◯: There is absolutely no unplated area. In addition, no peeling occurred in a cross-cut peel test using cellophane tape. △: There was absolutely no unplated area, but peeling occurred in a cross-cut peel test using cellophane tape. ×: There were areas where the plating was not adhered, and peeling occurred in a cross-cut peeling test using cellophane tape. (V) Long-term durability Plate-shaped test pieces measuring 50 mm in length, 100 mm in width and 1 mm in thickness were obtained by the method described below and plated under the conditions described below. They were then subjected to a treatment in an 80°C / 85% RH environment for 1,000 hours, after which an adhesion evaluation was carried out in the same manner as in (iii). ◯: There is absolutely no unplated area. In addition, no peeling occurred in a cross-cut peel test using cellophane tape. △: There was absolutely no unplated area, but peeling occurred in a cross-cut peel test using cellophane tape. ×: There were areas where the plating was not adhered, and peeling occurred in a cross-cut peeling test using cellophane tape. (VI) Flame retardant Tests were carried out using 1.5 mm thick test pieces prepared according to the following method in accordance with the UL94 standard. Based on the test results, the test pieces were rated as UL-94 V-0, V-1, V-2, or Not-V. The flame retardancy of the resin composition of the present invention must be V-0.
[0309] [Examples 1 to 18, Comparative Examples 1 to 6] (Creating evaluation specimens) Aromatic polycarbonate resin, circuit formation stabilizer, flame retardant, fluorine-containing drip prevention agent and various additives were mixed in a blender in the amounts shown in Tables 2 and 3, and then melt-kneaded using a vented twin-screw extruder to obtain pellets. The various additives used were premixed with aromatic polycarbonate resin in advance at a concentration of 10 to 100 times the amount of each additive, and then the entire mixture was mixed using a blender. For extrusion, a vented twin-screw extruder with a diameter of 30 mm (TEX30α-38.5BW-3V, Japan Steel Works, Ltd.) was used, and the screw rotation speed was 230 rpm, the discharge rate was 25 kg / h, the vent vacuum degree was 3 kPa, and the extrusion temperature was 300°C from the first feed port to the second feed port and 310°C from the second feed port to the die portion to obtain pellets. The polycarbonate resin and additives were fed into the extruder from the first feed port. The first feed port here refers to the feed port farthest from the die. The obtained pellets were dried in a hot air circulation dryer at 120°C for 5 hours, and then molded into test pieces for evaluation using an injection molding machine (SG-150U, manufactured by Sumitomo Heavy Industries, Ltd.) under molding conditions of a cylinder temperature of 300°C and a mold temperature of 80°C.
[0310] The adhesion and long-term durability of the molded products were evaluated after plating according to the following conditions: For the plating process, the obtained test pieces were printed with a 1064 nm YVO4 laser using a Keyence MDX-2000 at a frequency of 80 kHz, a speed of 2 m / s, an output of 1.45 W, a laser spot diameter of 60 μm, and an overlap of 30 μm, with a width of 5 mm, and then the following operations were carried out. (a) Degreasing (5 minutes at 45°C) OPC Cleaner MIC* 150ml / L (b) Ultrasonic washing (2 minutes at room temperature) (c) Electroless copper (55℃, 10 minutes) OPC Copper MIC-ST* (d) Washing with water (1 minute) (e) Activation (30℃, 1 minute) ICP Accelerator 200ml / L, 35% hydrochloric acid 85ml / L (f) Washing with water (1 minute) (g) Electroless nickel (80℃, 10 minutes) ICP Nicoron GM-M 120ml / L, ICP Nicoron GM-1 50ml / L (h)Drying (Processing solutions marked with an * are product names of Okuno Chemical Industries Co., Ltd.) The evaluation results are shown in Tables 2 and 3. The components denoted by symbols in Tables 2 and 3 are as follows.
[0311] (Component A) A-1: Aromatic polycarbonate resin (polycarbonate resin powder with a viscosity average molecular weight of 15,500 made by a conventional method from bisphenol A and phosgene, Teijin Limited, Panlite CM-1000 (product name)) A-2: Aromatic polycarbonate resin (polycarbonate resin powder with a viscosity average molecular weight of 19,700 made by a conventional method from bisphenol A and phosgene, Teijin Ltd. Panlite L-1225WX (product name)) A-3: Aromatic polycarbonate resin (polycarbonate resin powder with a viscosity average molecular weight of 23,900 made by a conventional method from bisphenol A and phosgene, Teijin Ltd. Panlite L-1250WP (product name)) A-4: Polycarbonate-polydiorganosiloxane copolymer resin (viscosity average molecular weight 23,500, PDMS content 8.4%, PDMS polymerization degree 37)
[0312] (B component) B-1-1: A reactor equipped with a thermometer, a stirrer and a reflux condenser was placed under a nitrogen atmosphere by nitrogen substitution, and then 93.3 parts of 25% aqueous sodium hydroxide solution and 182 parts of ion-exchanged water were charged, and 11.8 parts of 1,1-bis(4-hydroxy)-3,3,5-trimethylcyclohexane (hereinafter referred to as BP-TMC), 39.9 parts of 4,4-bis(4-hydroxy-3-methylphenyl)propane (hereinafter referred to as BP-C), and 0.1 parts of sodium hydrosulfite were dissolved therein, and then 231 parts of methylene chloride were added. The reaction vessel was then purged with nitrogen for 10 minutes, and 25 parts of phosgene was blown in at 18-21°C over about 60 minutes with stirring. After the injection of phosgene was completed, 15.6 parts of a 25% aqueous sodium hydroxide solution and 1.05 parts of p-tert-butylphenol were added, stirring was resumed, and after emulsification, 0.05 parts of triethylamine was added and the reaction was terminated by stirring at 20-27°C for an additional hour. After the reaction was completed, the product was diluted with methylene chloride at room temperature and washed with water, and then acidified with hydrochloric acid and washed with water. Washing with pure water was repeated until the conductivity of the aqueous phase was almost the same as that of ion-exchanged water, and a methylene chloride solution of polycarbonate was obtained. Next, a separation chamber having a foreign matter outlet in the bearing section was placed in the reaction vessel. The polycarbonate was turned into flakes while distilling off the methylene chloride, and the liquid-containing flakes were subsequently pulverized and dried to obtain a powdered polycarbonate resin.
[0313] B-1-2: A powdery polycarbonate resin was obtained in the same manner as in B-1-1, except that 29.6 parts of BP-TMC and 24.9 parts of BP-C were used.
[0314] B-1-3: A reactor equipped with a thermometer, a stirrer and a reflux condenser was charged with 4,760 parts of 48% aqueous sodium hydroxide and 20,779 parts of ion-exchanged water, to which 4,271 parts of 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane and 8.54 parts of hydrosulfite were dissolved, followed by adding 15,945 parts of methylene chloride, and then blowing in 2,000 parts of phosgene over about 60 minutes at 15-25° C. with stirring. After the blowing in of phosgene was completed, 595 parts of an aqueous 48% sodium hydroxide solution and 86.6 parts of p-tert-butylphenol were added, stirring was resumed, emulsification was followed by adding 5.01 parts of triethylamine, and the mixture was further stirred at 26-33° C. for 1 hour to complete the reaction. After the reaction was completed, the product was diluted with methylene chloride and washed with water, then acidified with hydrochloric acid and washed with water, and further washed with water repeatedly until the conductivity of the aqueous phase was almost the same as that of ion-exchanged water to obtain a methylene chloride solution of polycarbonate. Next, this solution was passed through a filter with an opening of 0.3 μm, and further dropped into warm water in a kneader with an isolation chamber and a foreign matter outlet in the bearing part, and the polycarbonate was turned into flakes while distilling off the methylene chloride, and the liquid-containing flakes were subsequently crushed and dried to obtain a powdered polycarbonate resin.
[0315] B-1-4: A reactor equipped with a thermometer, a stirrer and a reflux condenser was placed under a nitrogen atmosphere by nitrogen substitution, and then 592 parts of 48% aqueous sodium hydroxide and 2,909 parts of ion-exchanged water were charged, and 135 parts of 1,1-bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane, 255 parts of BP-C and 1.1 parts of hydrosulfite were dissolved therein, and then 1,984 parts of methylene chloride were added. The reaction vessel was then purged with nitrogen for 10 minutes, and 240 parts of phosgene were blown in at 18-21°C over about 60 minutes under stirring. After the blowing of phosgene was completed, 74 parts of 48% aqueous sodium hydroxide and 81 parts of p-tert-butylphenol were added, stirring was resumed, and after emulsification, 0.5 parts of triethylamine was added, and the mixture was further stirred at 20-27°C for 1 hour to complete the reaction. After the reaction was completed, the product was diluted with methylene chloride at room temperature and washed with water, then acidified with hydrochloric acid and washed with water. Washing with pure water was repeated until the conductivity of the aqueous phase was almost the same as that of ion-exchanged water, and a methylene chloride solution of polycarbonate was obtained. Next, the mixture was dropped into warm water in a kneader with an isolation chamber having a foreign matter outlet in the bearing section, and the polycarbonate was turned into flakes while distilling off the methylene chloride. The liquid-containing flakes were then crushed and dried to obtain a powdered polycarbonate resin.
[0316] B-2-1: A reactor equipped with a thermometer, a stirrer and a reflux condenser was charged with 4,555 parts of 48% aqueous sodium hydroxide solution and 22,730 parts of ion-exchanged water, and 298 parts of 9,9-bis(4-hydroxyphenyl)fluorene, 1,820 parts of BP-C, 1,799 parts of 2,2-bis(4-hydroxyphenyl)propane (hereinafter referred to as BP-A), 71.0 parts of p-tert-butylphenol, and 7.94 parts of hydrosulfite were dissolved therein, and 13,415 parts of methylene chloride was added, and 2,000 parts of phosgene were blown in over about 70 minutes at 15 to 25° C. under stirring. After the blowing of phosgene was completed, 650 parts of aqueous 48% sodium hydroxide solution and 87.6 parts of p-tert-butylphenol were added, stirring was resumed, and 3.94 parts of triethylamine were added after emulsification, and the reaction was terminated by stirring at 28 to 35° C. for 1 hour. After the reaction was completed, the product was diluted with methylene chloride and washed with water, then hydrochloric acid was added to make it acidic and washed with water, and further washing with water was repeated until the conductivity of the aqueous phase was almost the same as that of ion-exchanged water, to obtain a methylene chloride solution of polycarbonate resin. Next, this solution was passed through a filter with a mesh size of 0.3 μm, and further passed through a warm water kneader with an isolation chamber and a foreign matter outlet in the bearing part. The polycarbonate was turned into flakes while distilling off the methylene chloride, and the liquid-containing flakes were subsequently crushed and dried to obtain a powdered polycarbonate resin.
[0317] B-2-2: 3844 parts of 48% sodium hydroxide aqueous solution and 22,380 parts of ion-exchanged water were charged into a reactor equipped with a thermometer, a stirrer and a reflux condenser, 1,992 parts (7.8 moles) of BP-C and 1,773 parts (7.8 moles) of BP-A were dissolved therein, 13,210 parts of methylene chloride were added, and 2,000 parts of phosgene were blown in over about 60 minutes at 15-25°C under stirring. After the blowing of phosgene was completed, 640 parts of 48% sodium hydroxide aqueous solution and 93.2 parts of p-tert-butylphenol were added, stirring was resumed, and after emulsification, 3.24 parts of triethylamine were added, and the reaction was terminated by stirring for 1 hour at 28-33°C. After the reaction was completed, the product was diluted with methylene chloride and washed with water, then acidified with hydrochloric acid and washed with water, and further washed with water repeatedly until the conductivity of the aqueous phase was almost the same as that of the ion-exchanged water, to obtain a methylene chloride solution of polycarbonate. Next, this solution was passed through a filter with 0.3 μm openings and further dropped into warm water in a kneader with an isolation chamber and a foreign matter removal port in the bearing section, and the polycarbonate was turned into flakes while distilling off the methylene chloride. The liquid-containing flakes were then crushed and dried to obtain a powdered polycarbonate resin.
[0318] (C component) C-1: Halogen-based flame retardant (Teijin Limited, FG-7000) C-2: Condensed phosphate ester flame retardant (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) C-3: Phosphazene (FP-110T manufactured by Fushimi Seisakusho Co., Ltd.) C-4: Potassium perfluoroalkanesulfonate (F-114P, manufactured by Dainippon Ink and Chemicals, Inc.) C-5: Silicone flame retardant (X-40-2600J, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0319] (D component) D-1: Polytetrafluoroethylene (Mitsubishi Chemical Corporation, Metablen A3750) D-2: Polytetrafluoroethylene (Shine Polymers, SN3307PF)
[0320] (E component) E-1: Circular cross-section glass fiber having composition 1 shown in Table 1 (fiber diameter 11 μm, cut length 3 mm, long diameter / short diameter ratio = 1.0) E-2: Non-circular cross-section glass fiber having composition 1 shown in Table 1 (fiber diameter 15 μm, cut length 3 mm, major axis 28 μm, minor axis 7 μm) E-3: Talc [Shokoyama Mining Co., Ltd. Victorilite TK-RC]
[0321] [Table 1]
[0322] (Other ingredients) S-1: Tris(2,4-di-tert-butylphenyl)phosphite (Adeka 2112) S-2: 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1,-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane (AO-80 manufactured by Adeka) UV: Benzotriazole-based ultraviolet absorber (Ciba Specialty Chemicals: Tinuvin 234) L: Low molecular weight polyethylene (Hiwax HW405MP (product name) manufactured by Mitsui Chemicals, Inc.) CB: Carbon black (RB-90003S manufactured by Koshigaya Chemical Industry Co., Ltd.)
[0323] [Table 2]
[0324] [Table 3]
[0325] From Tables 2 and 3, it can be seen that the formulation of the present invention can provide a polycarbonate resin composition that is excellent in strength, appearance, flame retardancy, and low dielectric properties, as well as good adhesion to thin metal films during circuit formation and long-term durability.
Claims
1. A molded circuit product for communication devices, comprising a polycarbonate resin composition, characterized in that it contains, relative to 100 parts by weight of (A) an aromatic polycarbonate resin excluding component B (component A), (B) 10 to 5,000 parts by weight of a circuit formation stabilizer (component B) containing at least one selected from the group consisting of (B-1) a compound (component B-1) containing 10 mol % or more of a carbonate structural unit represented by the following formula (4) and (B-2) a compound (component B-2) containing 10 mol % or more of a carbonate structural unit represented by the following formula (5) excluding component B-1, (C) 0.05 to 1,000 parts by weight of a flame retardant (component C), and (D) 0.1 to 50 parts by weight of a fluorine-containing drip prevention agent (component D). 【Chemistry 1】 (In the above general formula (4), R 1 and R 2 each independently represent an alkyl group having 1 to 6 carbon atoms or a halogen atom, R 3 and R 4 each independently represent a hydrogen atom, an alkyl group having 1 to 6 carbon atoms or a halogen atom, R 5 represents a halogen atom, an alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 3 to 20 carbon atoms, and n represents an integer from 0 to 10.) 【Chemistry 2】 (In the above general formula (5), R 1 and R 2 each independently represent a group selected from an alkyl group having 1 to 6 carbon atoms, an optionally substituted cycloalkyl group having 6 to 15 carbon atoms, an optionally substituted aryl group having 6 to 15 carbon atoms, and an optionally substituted aralkyl group having 7 to 15 carbon atoms; R 3 and R 4 each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an optionally substituted cycloalkyl group having 6 to 15 carbon atoms, an optionally substituted aryl group having 6 to 15 carbon atoms, an optionally substituted aralkyl group having 7 to 15 carbon atoms, an optionally substituted alkenyl group having 2 to 20 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an optionally substituted cycloalkoxy group having 6 to 20 carbon atoms, an optionally substituted aryloxy group having 6 to 15 carbon atoms, an optionally substituted aralkyloxy group having 7 to 15 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each, they may be the same or different, a and b are natural numbers of 1 to 3, and W is a single bond or at least one group selected from the group consisting of groups represented by the following general formula (2):
2. 2. A molded circuit product for communication devices comprising the polycarbonate resin composition according to claim 1, characterized in that component A is an aromatic polycarbonate resin containing 1 to 100% by weight of a polycarbonate-polydiorganosiloxane copolymer resin (component A-1) consisting of a polycarbonate block represented by the following formula (1) and a polydiorganosiloxane block represented by the following formula (3), and the polydiorganosiloxane content in 100% by weight of component A-1 is 0.05 to 20.0% by weight. 【Chemistry 3】 (In the above general formula (1), R 1 and R 2 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each of these groups, they may be the same or different, a and b each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula (2): 【Chemistry 4】 (In the above general formula (2), R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, c is an integer from 1 to 10, and d is an integer from 4 to 7. 【Chemistry 5】 (In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; e and f are each an integer of 1 to 4; p is a natural number; q is 0 or a natural number; and p+q is a natural number of 4 or more and 150 or less; and X is a divalent aliphatic group having 2 to 8 carbon atoms.
3. 3. A circuit molded product for communication devices comprising the polycarbonate resin composition according to claim 1 or 2, characterized in that component C contains at least one flame retardant selected from the group consisting of halogen-based flame retardants, condensed phosphate ester compounds, phosphazene compounds, organometallic salt-based flame retardants, and silicone-based flame retardants.
4. The circuit formation stabilizer according to any one of claims 1 to 3, characterized in that the component B-2 is at least one selected from the group consisting of: (B-2-1) a compound (B-2-1) composed of a structural unit (A) represented by the following formula (6), a structural unit (B) represented by the following formula (7), and a structural unit (C) represented by the following formula (8), in which the proportion of the structural unit (A) in the total structural units is 5 to 15 mol%, the proportion of the structural unit (B) is 20 to 60 mol%, and the proportion of the structural unit (C) is 25 to 75 mol%, and (B-2-2) a compound (B-2-2) composed of a repeating structural unit (B) represented by the following formula (7) and a repeating structural unit (C) represented by the following formula (8), in which the proportion of the structural unit (B) in the total structural units is 20 to 100 mol%, and the proportion of the structural unit (C) is 0 to 80 mol%. 【Chemistry 6】 (In the above general formula (6), R 1 and R 2 are each independently a hydrogen atom, a hydrocarbon group having 1 to 9 carbon atoms which may contain an aromatic group, or a halogen atom. 【Chemistry 7】 (In the above general formula (7), R 3 and R 4 are each independently an alkyl group having 1 to 6 carbon atoms or a halogen atom. X is a single bond, a substituted or unsubstituted alkylene group, a substituted or unsubstituted alkylidene group, a sulfur atom, or an oxygen atom. 【Chemistry 8】 (In the above general formula (8), W is a single bond, a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkylidene group having 1 to 10 carbon atoms.)
5. 5. A molded circuit article for communication devices comprising the polycarbonate resin composition according to claim 4, characterized in that the structural unit (A) is a structural unit derived from 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, the structural unit (B) is a structural unit derived from 2,2-bis(4-hydroxy-3-methylphenyl)propane, and the structural unit (C) is a structural unit derived from 2,2-bis(4-hydroxyphenyl)propane.
6. 6. A molded circuit article for communication devices comprising the polycarbonate resin composition according to any one of claims 1 to 5, characterized in that Component B-1 is a compound containing 20 mol % or more of structural units derived from 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane or 1,1-bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane.
7. 7. A molded circuit article for communication devices comprising the polycarbonate resin composition according to any one of claims 1 to 6, characterized in that it contains 1 to 2,500 parts by weight of an inorganic filler (E) (Component E) per 100 parts by weight of Component A.
8. 8. A molded circuit article for communication devices comprising the polycarbonate resin composition according to claim 7, wherein component E is at least one inorganic filler selected from the group consisting of glass, carbon fiber, talc, mica and wollastonite.
9. 9. A molded circuit product for communication devices comprising the polycarbonate resin composition according to claim 7 or 8, characterized in that component E is at least one glass fiber selected from the group consisting of (E-1) noncircular cross section glass fiber (component E-1) having a number average fiber length of 30 to 5000 μm, a ratio of the major axis to the minor axis of the cross section (major axis / minor axis) of 2.0 to 10.0, and a fiber diameter of 3.0 to 35.0 μm when the cross section is converted into a perfect circle, and (E-2) circular cross section glass fiber (component E-2) having a number average fiber length of 30 to 5000 μm and an average fiber diameter of 7.0 to 13.0 μm.
10. The E component is 52.0 to 57.0% by weight of SiO based on the total amount of glass fibers. 2 , 13.0 to 17.0 wt.% Al 2 O 3 , 15.0 to 21.5% by weight of B 2 O 3 , 2.0 to 6.0% by weight of MgO, 2.0 to 6.0% by weight of CaO, 1.0 to 4.0% by weight of TiO 2 and less than 1.5 wt.% F 2 and Li 2 O, Na 2 O and K 2 10. A molded circuit article for communication devices comprising the polycarbonate resin composition according to any one of claims 7 to 9, characterized in that the glass fiber contains less than 0.6% by weight of O in total.
11. 11. A molded circuit product for communication devices, which is made of the polycarbonate resin composition according to any one of claims 1 to 10 for forming circuits.
Citation Information
Patent Citations
Flame resistant aromatic polycarbonate resin composition
JP2007100023A
Polycarbonate resin composition
JP2011105914A
Polycarbonate resin composition and molded article composed of the same
JP2012072338A
Aromatic polycarbonate resin composition and resin molding obtained by molding the same
JP2013023532A
Flame retardant glass fiber-reinforced polycarbonate resin composition
JP2015059138A